Cerium(III) carbonate preparations

JP7641006B2Active Publication Date: 2025-03-06RGT UNIV OF CALIFORNIA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021563429
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-23
Filing Date
2020-04-23
Publication Date
2025-03-06
Estimated Expiration
2040-04-23

Smart Images

  • Figure 0007641006000005
    Figure 0007641006000005
  • Figure 0007641006000006
    Figure 0007641006000006
  • Figure 0007641006000007
    Figure 0007641006000007
Patent Text Reader

Abstract

In particular, the present disclosure provides formulations containing cerium(III) carbonate and methods for making cerium(III) carbonate. In some embodiments, the present disclosure provides methods for passivating the photodegradation of organic compounds using cerium(III) carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This PCT application claims priority to U.S. Provisional Patent Application Serial No. 62 / 837,657, filed April 23, 2019, the entire contents of which are incorporated herein by reference. [Background technology]

[0002] Organic compounds are susceptible to photodegradation and some compounds, such as pigments (e.g., TiO2), are well-known photocatalysts. The photocatalytic activity initiated and promoted by pigments is due to the generation of reactive oxygen species (ROS), which are known to cause the decomposition of organic compounds. Therefore, to reduce the photocatalytic activity, pigments are commonly modified with a thin overcoat (approximately 5-10 nm) of metal oxides, such as SiO2, Al2O3, ZrO2 or mixtures thereof. These metal oxides are responsible for the reduction of the photocatalytic activity of the pigments and / or the generation of reactive oxygen species (ROS), such as hydroxyl radicals (OH), superoxide radical anions (O2), etc. - and hydrogen peroxide, H2O2 (all of which photolyze and oxidatively degrade organic compounds). Summary of the Invention [Problem to be solved by the invention]

[0003] There is a need in the art to inhibit the photodegradation of organic compounds. The present disclosure is directed to this, as well as other important objectives. [Means for solving the problem]

[0004] The present disclosure provides cerium(III) carbonate of formula Ce2(CO3)3·xH2O, where x is zero or a positive number, wherein the cerium(III) carbonate releases at least 27.6 weight percent (wt%) of CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate is substantially free of cerium(IV) and / or substantially free of a cerium oxide phase.

[0005] The present disclosure provides a formulation comprising cerium(III) carbonate and an organic compound susceptible to photolysis. In some embodiments, the present disclosure provides a formulation comprising cerium(III) carbonate, an organic compound susceptible to photolysis, and a photocatalytically active pigment. In some embodiments, the present disclosure provides a formulation comprising cerium(III) carbonate, an organic compound susceptible to photolysis, a photocatalytically active pigment, and water.

[0006] The present disclosure provides a method of producing cerium (III) carbonate by (i) mixing a carbonate salt with water to form a first solution, (ii) mixing a cerium (III) salt with water to form a second solution, (iii) mixing the first and second solutions to form a third solution having a pH of 9.2 or less, and (iv) centrifuging the third solution to form cerium (III) carbonate. In some embodiments, the carbonate salt is ammonium carbonate and the cerium (III) salt is ammonium cerium (III) nitrate tetrahydrate. In some embodiments, the cerium (III) carbonate is Ce2(CO3)3·4H2O. In some embodiments, the third solution has a pH of about 9.0 to 9.2. Alternatively, the present disclosure provides a method for producing cerium(III) carbonate by (i) mixing two solids including a carbonate salt and a cerium(III) salt (without adding water), (ii) washing off excess salt with water, and centrifuging the resulting mixture to provide solid cerium(III) carbonate.

[0007] The present disclosure provides a method for preparing the formulation by mixing a cerium(III) carbonate source material with an organic compound susceptible to photodecomposition.

[0008] These and other embodiments are described in this disclosure. [Brief description of the drawings]

[0009] [Figure 1A-1C] 1A-1C are (i) plots of the photodegradation of MB dye under 254 nm light at pH 9.1 using 1 mg of P25 photocatalyst in the presence of 2.5 mg of soluble (dissolved) ammonium cerium(III) nitrate (Figure 1A); (ii) plots of the photodegradation of MB dye under 254 nm light at pH 9.1 using 1 mg of P25 photocatalyst in the presence of 10 mg of soluble (dissolved) ammonium cerium(III) nitrate (Figure 1B); and (iii) plots of the photodegradation of MB dye under 254 nm light at pH 9.1 using 1 mg of P25 photocatalyst in the presence of 1 mg of insoluble Ce(III)-P25 (Figure 1C). [Figure 2A-2B] Figure 2A is a photograph showing that the color of pure SiO2 powder remains unchanged after Ce(III) deposition on SiO2, and Figure 2B is a plot of the photodegradation (under 254 nm light) of methylene blue (MB) dye (10 mL, 10-5 M) by 50 mg of P25 in the presence of 5 mg of Ce(III)-SiO2 with a surface area ratio of 1:0.877. [Figure 3A-3B] FIG. 3A is a photograph showing rutile TiO2 powder before (left sample) and after (right sample) deposition of Ce(III) on the surface of the rutile TiO2 powder, and FIG. 3B is a plot of the kinetics of decomposition of 10-5 M MB organic dye by 2 mg of P25 in the presence of 5.7 mg of Ce(III)-TiO2 under 254 nm light. [Figure 4A-4B] 4A-4B are photographs showing that there is no difference in color between unmodified Ti-Pure R706 (FIG. 4A) and Ce(III)-R706 (FIG. 4B).

[0010] [Figure 5A-5B]5A-5B are plots of the kinetics of the decomposition of 10-5 M MB organic dye by P25 in the presence of Ce(III)1h-R706 (FIG. 5A) and in the presence of unmodified R706 (FIG. 5B). [Figure 6A-6B] Figures 6A-6B are plots of the kinetics of decomposition of 10-5 M MB organic dye in the presence of various ratios of P25 and Ce(III)-R706 (Figure 6A) and the kinetics of decomposition of 10-5 M MB organic dye in the presence of various ratios of P25 and Ce(III) / Ce(IV-R706) (Figure 6B). [Figure 7A-7B] 7A-7B show UV-visible spectra showing the degradation of Congo Red (CR) dye in a coating prepared with 10% P25 and 90% Ce(III)-R706 before and after 6 hours of sunlight exposure (FIG. 7A) and in a coating prepared with 10% P25 and 90% unmodified Ti-Pure R706 before and after 6 hours of sunlight exposure (FIG. 7B). [Figure 8] FIG. 8 is a photograph of white cerium (III) carbonate powder. [Figure 9] Figure 9 shows the TGA patterns of cerium(III) carbonate synthesized as described in Examples 3 and 6 and several commercially available cerium(III) carbonate samples. All samples were dried at 80°C for 16 hours before analysis.

[0011] [Figure 10] Figure 10 is a plot of the kinetics of the decomposition (under 254 nm light) of 10-5 M MB organic dye in the presence of 2 mg P25, 11.4 mg unmodified R706, and 1 mg Ce2(CO3)3·4H2O added separately. [Figures 11A-11C]11A-11C show the UV-visible spectra of the CR organic dye before and after sunlight exposure for a coating prepared with R706 and (i) 0 wt% Ce(III) carbonate (FIG. 11A); the UV-visible spectra of the CR organic dye before and after sunlight exposure for a coating prepared with R706 and (ii) 2 wt% cerium(III) carbonate (FIG. 11C); and the UV-visible spectra of the CR organic dye before and after sunlight exposure for a coating prepared with R706 and (iii) 5 wt% Ce(III) carbonate relative to the mass of R706 (FIG. 11C). [Figures 12A-12C] 12A-12C show the UV-visible spectra of CR dye before and after sunlight exposure for a coating prepared with rutile TiO2 and (i) 0 wt% Ce(III) carbonate (FIG. 12A); the UV-visible spectra of CR dye before and after sunlight exposure for a coating prepared with rutile TiO2 and (ii) 2 wt% Ce(III) carbonate (FIG. 12B); and the UV-visible spectra of CR dye before and after sunlight exposure for a coating prepared with rutile TiO2 and (iii) 5 wt% Ce(III) carbonate with respect to the TiO2 mass (FIG. 12C). [Figures 13A-13C] 13A-13C show plots of the kinetics of the degradation (under 254 nm light) of 10-5 M MB organic dye in the presence of 2 mg P25, 11.4 mg unmodified R706, and separately added (i) 1 mg Ce2(CO3)3·xH2O (Alfa Aesar) (FIG. 13A); (ii) 5 mg Ce2(CO3)3·xH2O (Sigma Aldrich) (FIG. 13B); and (iii) 5 mg Ce2(CO3)3·xH2O (ACROS Organics) (FIG. 13C). [Figure 14]Figure 14 provides ATR-FTIR spectra of different cerium(III) carbonate materials, including those synthesized in Examples 3 and 6, as well as commercial samples from Sigma Aldrich, Acros Organics, and Alfa Aesar (samples were dried at ambient conditions for 48 hours prior to analysis). The vertical arrow indicates the frequency of the 1410 cm-1 band, which represents weakly electrostatically attached carbonate, and is depicted at the top as an eye guide.

[0012] [Figure 15A-15B] Figure 15A provides photodegradation kinetic data for 10 mL of an aqueous solution of 10 M MB dye exposed to 254 nm light for up to 60 min under a photoreactor setup. Figure 15B provides photodegradation kinetic data for 10 mL of an aqueous solution of 10 M MB dye and 1 mg Ce2(CO3)3·4H2O (synthesized as described in Example 3) exposed to 254 nm light for up to 60 min under a photoreactor setup. [Figure 16] Figure 16 is a plot of the kinetics of decomposition (under 254 nm light) of 10-5 M MB organic dye in the presence of 2 mg P25, 11.4 mg unmodified R706, and 1 mg of another phase of Ce2(CO3)3·4H2O. [Figure 17] Figure 17 is a UV-visible spectrum of MB dye extracted from a ZnO-based sunscreen film (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) without added UV protection agents. The time in the inset refers to the UV exposure time in the photoreactor. [Figure 18A-18B]Figure 18A is the UV-Vis spectrum of MB dye extracted from a ZnO-based sunscreen film (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) with 0.5 wt% added Ce2(CO3)3·6H2O. Figure 18B is the UV-Vis spectrum of MB dye extracted from a ZnO-based sunscreen film (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) with 1.5 wt% added Ce2(CO3)3·6H2O. The time in the inset refers to the UV exposure time in the photoreactor. [Figure 19A-19B] Figure 19A is a UV-Vis spectrum of MB dye extracted from a ZnO-based sunscreen film (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) with 0.5 wt% added ZnO (NANOBYK-3840). Figure 19B is a UV-Vis spectrum of MB dye extracted from a ZnO-based sunscreen film (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) with 1.5 wt% added ZnO (NANOBYK-3840). The time in the inset refers to the UV exposure time in the photoreactor.

[0013] [Figure 20] FIG. 20 is a plot of the percentage of MB degradation in a sunscreen film on a filter paper after 4 hours of UV irradiation in a photoreactor versus the amount of Ce2(CO3)3 6H2O and ZnO (NANOBYK-3840) added in the sunscreen (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50). [Figure 21A-21B]Figure 21A is the UV-visible spectrum of CR dye extracted from a ZnO-based sunscreen film (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) with no added photoprotectant. Figure 21B is the UV-visible spectrum of CR dye extracted from a ZnO-based sunscreen film (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) with 1.5 wt% added Ce2(CO3)3·6H2O. The time in the inset refers to the UV exposure time in the photoreactor. [Fig. 22A-22B] Figure 22A shows the UV-visible spectrum of CR dye extracted from a TiO2-based sunscreen film (Neutrogena® Broad Spectrum Mineral Sunscreen SPF 60+) with no added photoprotectant and Figure 22B shows the UV-visible spectrum of CR dye extracted from a TiO2-based sunscreen film (Neutrogena® Broad Spectrum Mineral Sunscreen SPF 60+) with 3.0 wt% added Ce2(CO3)3·6H2O. [Fig. 22C-22D] FIG. 22C is a UV-visible spectrum of CR dye extracted from a TiO2-based sunscreen film (Neutrogena® Broad Spectrum Mineral Sunscreen SPF 60+) doped with 3.0 wt% Ce2(CO3)3·xH2O commercially available from Acros Organics. FIG. 22D is a UV-visible spectrum of CR dye extracted from a TiO2-based sunscreen film (Neutrogena® Broad Spectrum Mineral Sunscreen SPF 60+) with 3.0 wt% doped ZnO (NANOBYK-3840). The time in the inset refers to the UV exposure time in the photoreactor. [Figure 23A-23B]Figure 23A is the UV-visible spectrum of CR dye extracted from a TiO2-based sunscreen film (Neutrogena® Broad Spectrum Mineral Sunscreen SPF 60+) containing 5.0 wt% added Ce2(CO3)3·6H2O. Figure 23B is the UV-visible spectrum of CR dye extracted from a TiO2-based sunscreen film (Neutrogena® Broad Spectrum Mineral Sunscreen SPF 60+) containing 3.0 wt% ZnO (NANOBYK-3840). The time in the inset refers to the UV exposure time in the photoreactor. [Figure 24] FIG. 24 is a plot of the percentage of CR decomposition in a sunscreen film on filter paper after 4 hours of UV irradiation in a photoreactor versus the amount of Ce2(CO3)3 6H2O and ZnO (NANOBYK-3840) added in the sunscreen (Neutrogena® Broad Spectrum Mineral Sunscreen SPF 60+).

[0014] [Fig. 25A-25B] Figure 25A is the UV-visible spectrum of MB dye extracted from an oxacrylene-based sunscreen film (Blue Lizard® Kids Australian Sunscreen SPF 30+) without added UV protection agents. Figure 25B is the UV-visible spectrum of MB dye extracted from a ZnO-based sunscreen film (Blue Lizard® Kids Australian Sunscreen SPF 30+) with 1.5 wt% Ce2(CO3)3·6H2O added as synthesized in Example 3. The time in the inset refers to the UV exposure time in the photoreactor. [Figure 26A-26B] Figure 26A is a microscopic image of rat cells (micron size) before treatment with the preferred cerium carbonate Ce2(CO3)3·6H2O. Figure 26B is a microscopic image of rat cells (micron size) after treatment with the preferred cerium carbonate Ce2(CO3)3·6H2O. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Detailed Description definition "Cerium(III) carbonate" refers to a material consisting of Ce2(CO3)3. In some embodiments, the cerium(III) carbonate is substantially free of cerium(IV) and / or cerium oxide phases. In some embodiments, Ce2(CO3)3 is white in appearance. In some embodiments, the cerium(III) carbonate is substantially free of cerium(IV) if it is white in appearance and has no yellowish tinge. In some embodiments, Ce2(CO3)3 is Ce2(CO3)3·xH2O, where x is zero or a positive number. In some embodiments, the positive number is an integer between 1 and 6. In some embodiments, Ce2(CO3)3·xH2O is Ce2(CO3)3·4H2O. In some embodiments, thermogravimetric analysis is used to determine if the cerium(III) carbonate is substantially free of cerium oxide phases. cerium(III) carbonate is preferred because it releases a higher wt% of CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate, compared to cerium(III) carbonate that also contains a cerium oxide phase. The amount of CO2 released upon heating a sample of cerium(III) carbonate is measured by thermogravimetric analysis, as described below. In some embodiments, the cerium(III) carbonate releases at least 21.9 wt% of CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 27 wt% of CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 27.5 wt% of CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 27.6 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 28.0 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 28.5 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate.In some embodiments, the cerium (III) carbonate releases at least 29.0 wt% CO2 during thermogravimetric analysis, as normalized to the dry mass of the cerium (III) carbonate. In some embodiments, the cerium (III) carbonate contains at least 5.7 wt% carbon and at least 0.9 wt% hydrogen, as measured by CHN analysis. In some embodiments, the cerium (III) carbonate contains at least 6.5 wt% carbon and at least 1.45 wt% hydrogen, as measured by CHN analysis. In some embodiments, the cerium (III) carbonate contains about 6.7 wt% carbon and about 1.76 wt% hydrogen, as measured by CHN analysis. In some embodiments, the cerium (III) carbonate has a peak at 1410 cm as measured by ATR-FTIR. -1 and 1468cm -1 In some embodiments, the cerium(III) carbonate has a peak intensity ratio of 1410 cm to 1410 cm when measured by ATR-FTIR. -1 and 1468cm -1 In some embodiments, the cerium(III) carbonate has a peak intensity ratio of 1410 cm to 1410 cm when measured by ATR-FTIR. -1 Peak intensity at 1468cm -1 The ratio of peak intensities at is about 0. In some embodiments, the cerium(III) carbonate is substantially insoluble in water.

[0016] "Cerium (III) carbonate source material" refers to cerium (III) carbonate obtained from a commercial supplier, or produced by methods known in the art, or produced by methods described herein. In some embodiments, the cerium (III) carbonate source material is substantially free of cerium (IV) and / or cerium oxide phases. In some embodiments, the cerium (III) carbonate source material is white in appearance. In some embodiments, the cerium (III) carbonate source material is substantially free of cerium (IV) if it is white in appearance and has no yellowish tinge. In some embodiments, the cerium (III) carbonate source material releases at least 21.9 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate source material releases at least 27 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate source material releases at least 27.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate source material releases at least 27.6 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate source material releases at least 28.0 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate source material releases at least 28.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate source material releases at least 29.0 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate source material comprises at least 5.7 wt.% carbon and at least 0.9 wt.% hydrogen as determined by CHN analysis. In some embodiments, the cerium (III) carbonate source material comprises at least 6.5 wt.% carbon and at least 1.45 wt.% hydrogen as determined by CHN analysis.In some embodiments, the cerium (III) carbonate source material contains about 6.7 wt. % carbon and about 1.76 wt. % hydrogen as measured by CHN analysis. In some embodiments, the cerium (III) carbonate source material contains about 1.4 wt. % carbon and about 1.76 wt. % hydrogen as measured by ATR-FTIR analysis. -1 and 1468cm -1 In some embodiments, the cerium(III) carbonate source material has a peak intensity ratio of 1410 cm to 1410 cm as measured by ATR-FTIR of about 1.3 or less. -1 and 1468cm -1 In some embodiments, the cerium(III) carbonate source material has a peak intensity ratio of 1410 cm to 1420 cm as measured by ATR-FTIR. -1 and 1468cm -1 In some embodiments, the cerium(III) carbonate source material has a peak intensity ratio of 1410 cm to 1420 cm as measured by ATR-FTIR of about 0.9 or less. -1 Peak intensity at 1468cm -1 is about 0. In some embodiments, the cerium (III) carbonate source material is Ce2(CO3)3·xH2O, where x is 0 or a positive integer. In some embodiments, x is 0, 1, 2, 3, 4, 5, or 6. In some embodiments, the cerium (III) carbonate source material is Ce2(CO3)3·4H2O. In some embodiments, the cerium (III) carbonate source material is substantially insoluble in water.

[0017] "Thermogravimetric analysis" is an analytical method based on measuring the mass of a sample of cerium carbonate while it is heated in dry air at a ramp rate of 5°C / min, during which the sample thermally decomposes to synthesize cerium oxide and CO2 at temperatures ranging from 200°C to 575°C. Herein, the amount of CO2 released was calculated by subtracting the mass of the sample at 200°C from the mass at 575°C, and this mass difference was divided by the mass of the sample at 200°C to obtain the mass fraction of released CO2 release normalized to the dry mass of cerium carbonate. In this way, the trend in the amount of CO2 released from cerium carbonate, as measured by thermogravimetric analysis, generally coincides with the trend in the carbon content of cerium carbonate, as measured by CHN analysis, across different samples. Thermogravimetric analysis is further described in Liu et al., J. Cryst. Growth, 206:88-92 (1999) and Zhai et al., Mater. Lett., 61:1863-1866 (2007).

[0018] "CHN analysis" refers to the analysis of carbon (C), hydrogen (H) and nitrogen (N) in a compound or composition. CHN analysis can be performed by scientific instruments known in the art, such as, for example, a 2400 CHN elemental analyzer from Perkin Elmer, a CE440 elemental analyzer from Exeter Analytical, etc. CHN analysis is well known in the art.

[0019] "Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy" and "ATR-FTIR" are spectroscopic techniques that measure the changes that occur in an internally reflected infrared beam when the beam strikes a sample. ATR-FTIR is well known in the art and is described, for example, in the technical note "FT-IR Spectroscopy, Attentuated Total Reflectance (ATR)" by Perkin Elmer (2005).

[0020] "White" refers to compounds and compositions that are white in appearance and / or a mixture of all wavelengths of light in the visible spectrum, e.g., from about 380 nm to about 750 nm. The term "white in appearance" encompasses all shades of white, such as pure white, alabaster, cream, eggshell, ivory, Navajo white, vanilla, and the like. In embodiments, the term "white in appearance" encompasses all shades of white that are not visually yellowish. In embodiments, the term "white in appearance" is a brilliant white that has no absorbance in the yellow region of the visible spectrum (e.g., no absorbance at wavelengths from about 565 nm to about 590 nm) as determined by solid-state UV-visible spectroscopy (such measurements are known to those skilled in the art and can be made, for example, using a diffuse reflectance accessory; see J. Am. Chem. Soc. 2004, 126, 16478-16486).

[0021] "Substantially insoluble in water" refers to a compound that has a solubility in water of less than 1 wt% (e.g., cerium(III) carbonate). In some embodiments, it refers to a compound that has a solubility in water of less than 0.5 wt% (e.g., cerium(III) carbonate). In some embodiments, it refers to a compound that has a solubility in water of less than 0.25 wt% (e.g., cerium(III) carbonate). In some embodiments, it refers to a compound that has a solubility in water of less than 0.1 wt% (e.g., cerium(III) carbonate).

[0022] "Average particle size of cerium(III) carbonate" refers to the radius of gyration and is measured by electron microscopy. The cerium(III) carbonate can be of any particle size in the formulations described herein. In some embodiments, the average particle size of cerium(III) carbonate is from about 1 nanometer to about 100 microns. In some embodiments, the average particle size of cerium(III) carbonate is from about 10 nanometers to about 10 microns. In some embodiments, the average particle size of cerium(III) carbonate is from about 10 nanometers to about 1 micron. In some embodiments, the average particle size of cerium(III) carbonate is from about 30 nanometers to about 500 nanometers. In some embodiments, the average particle size of cerium(III) carbonate is from about 40 nanometers to about 300 nanometers. In some embodiments, the average particle size of cerium(III) carbonate is from about 1 nanometer to about 80 nanometers. In some embodiments, the average particle size of cerium(III) carbonate is from about 1 nanometer to about 50 nanometers. In some embodiments, the average particle size of the cerium (III) carbonate is from about 1 nanometer to about 80 nanometers.In some embodiments, the average particle size of the cerium (III) carbonate is from about 1 nanometer to about 40 nanometers.

[0023] "Photocatalytically active pigment" refers to a pigment that accelerates the rate of photodecomposition of an organic compound. Photocatalytically active pigments can catalyze certain chemical reactions when irradiated with light of the appropriate wavelength. For example, in the presence of light and / or air and / or water, the surface of the photocatalytically active pigment can synthesize extremely powerful oxidants that cause the conversion and / or decomposition of organic substances. Such organic substances are referred to as organic compounds susceptible to photodecomposition in this disclosure. In some embodiments, the photocatalytically active pigment is a metal oxide, a metal sulfide, or a combination thereof. In some embodiments, the photocatalytically active pigment is a metal oxide. In some embodiments, the photocatalytically active pigment is titanium dioxide, zinc oxide, cerium oxide, zirconium oxide, tungsten oxide, vanadium oxide, tin oxide, nickel oxide, copper oxide, molybdenum oxide, tungsten sulfide, cadmium sulfide, cadmium selenide, zinc sulfide, or a combination of two or more thereof. In some embodiments, the photocatalytically active pigment is titanium dioxide. In some embodiments, the highly potent oxidizing agents are ROS.

[0024] "Same phase" refers to the cerium(III) carbonate being precipitated in the presence of an existing surface of a different phase, e.g., the surface of an inorganic oxide particle such as a photocatalytically active pigment (e.g., TiO2). In some "same phase" embodiments, the cerium(III) carbonate at least partially coats the inorganic oxide particle surface such as a photocatalytically active pigment (e.g., TiO2). In some "same phase" embodiments, the cerium(III) carbonate is ionically or covalently bound to the inorganic oxide particle surface such as a photocatalytically active pigment (e.g., TiO2).

[0025] By "separate phase" it is meant that the cerium carbonate does not precipitate in proximity to an existing surface of a different phase (e.g., the surface of an inorganic oxide particle or a photocatalytically active pigment), but rather precipitates to form a unique phase of cerium(III) carbonate that is independent of their proximity to the pigment or photocatalytic particles, and which, by virtue of its insolubility in water, remains a unique, separate particle in the aqueous dispersion.

[0026] "Substantially free of cerium(IV)" refers to a formulation or composition that is substantially free of cerium(IV). In some embodiments, the formulation contains less than 50 wt% cerium(IV). In some embodiments, the formulation contains less than 10 wt% cerium(IV). In some embodiments, the formulation contains less than 1.0 wt% cerium(IV). In some embodiments, the formulation contains less than 0.5 wt% cerium(IV). In some embodiments, the formulation contains no detectable amount of cerium(IV).

[0027] "Cerium oxide" or "cerium oxide phase" refers to cerium oxide as defined below. In some embodiments, cerium oxide contains a substance represented by the chemical formula CeO y (where y is between 1.5 and 2). Cerium oxide has a yellowish-white appearance when y = 2 and a golden yellow appearance when y = 1.5. While CeO2 crystallizes in a fluorite structure, in the substoichiometric oxides where 1.5 < y < 2, typically a mixture of Ce(III) and Ce(IV) and oxygen vacancies are present in the structure. In some embodiments, "cerium oxide" includes a hydrated oxide structure represented by the chemical formula CeO y ·aH2O (where a is typically a number less than 10 and y is between 1.5 and 2). In some embodiments, "cerium oxide" has the chemical formula Ce(O) x (OH) zCerium oxide oxyhydroxides include those having a molar ratio of Ce to H2O of less than 10, where (x+2z)=1.5-2. Cerium oxide oxyhydroxides can be hydrated, and in these structures, the typical molar ratio of Ce to H2O is less than 10. Many phases of cerium oxide have been identified, and some of these phases can be represented on the Ce2O3-CeO2 phase diagram (see Chem. Rev. 1998, 98, 1479-1514). Some known phases of cerium oxide include, but are not limited to, cubic cerium oxide, cubic ceria, cubic cerianite, triclinic cerium oxide, rhombohedral cerium oxide, and triclinic cerium oxide. Generally, the relative amounts of substoichiometric oxide and Ce(III) increase as the cerium oxide nanoparticle size decreases, with a Ce(III) to Ce(IV) ratio close to 0.75 reported for 4.5 nm cerium oxide nanoparticles by X-ray photoelectron spectroscopy (see Nanoscale 2018, 10, 6971-6980). It is generally known that cerium oxide forms mixtures with carbonates (see references 305-311 in Chem. Rev. 2016, 116, 5987-6041), and for the purposes of this disclosure, it is undesirable for the acid-cerium phase to be present as a mixture in the cerium carbonate material. Examples of such mixtures, which for the purposes of this disclosure are also cerium oxides, include, but are not limited to, cerium oxide carbonate hydrate, hydroxylbastnasite, cerium carbonate hydroxide hydrate, cerium oxalate carbonate hydrate, cerium aquacarbonate oxalate hydrate, and orthorhombic cerium carbonate hydroxide. Characterization of CeO2 can be performed by powder X-ray diffraction, but this method is known in the art to be insensitive to the presence and detection of substoichiometric oxides of ceria (see Chem. Rev. 116, pp. 5989-5990; Rev. 2016, 116, 5987-6041). Nevertheless, those skilled in the art will appreciate that powder X-ray diffraction data for various cerium oxide structures are publicly available from the International Center for Diffraction Data (ICDD).Some of these structures are ICDD codes (01-072-6357), (01-075-7751), (01-075-7749), (01-075-8371), (01-071-4807), (01-075-9470), (01-075-5980), (01-073-9516), (01-073 -6328), (01-071-4199), (01-089-8429), (01-089-8430), (01-075-7752), (03-065-2975), (01-089-8436), (01-081-0792), (03-065-5923), (01-075-7750), (01-08 9-8435), (01-089-8431), (01-073-6318), (01-075-7754), (01-071-0567), (01-089-8432), (01-075-7755), (01-075-7758), (01-075-7753), (01-075-7757), (01-0 75-7756), (01-089-8434), (00-046-0369), (00-032-0189), (00-028-0897), (01-089-2794), (00-051-0549), (00-43-0602), (00-44-0617), and (00-041-0013). Those skilled in the art will appreciate that it is possible to test a cerium carbonate material for the absence of a cerium oxide phase by powder x-ray diffraction by confirming that the powder x-ray pattern of the cerium carbonate material lacks peaks corresponding to one or more of the cerium oxide structures listed above among other cerium oxide structures not listed. However, as noted above, this method lacks sensitivity to certain cerium oxides, such as substoichiometric cerium oxides, and amorphous cerium oxides. For purposes of this disclosure, a method for assessing the absence of cerium oxide phases in a cerium carbonate sample is a white color in appearance (i.e., lack of yellowness) along with a high wt % CO release as assessed by thermogravimetric analysis of the cerium carbonate.

[0028] "Substantially free of cerium oxide" or "substantially free of cerium oxide phases" refers to a formulation or composition that is substantially free of cerium oxide phases. In some embodiments, the formulation contains less than 50 wt% cerium oxide. In some embodiments, the formulation contains less than 10 wt% cerium oxide. In some embodiments, the formulation contains less than 5 wt% cerium oxide. In some embodiments, the formulation contains less than 2 wt% cerium oxide. In some embodiments, the formulation contains less than 1.0 wt% cerium oxide. In some embodiments, the formulation contains less than 0.5 wt% cerium oxide. In some embodiments, the formulation contains less than 0.1 wt% cerium oxide. In some embodiments, the formulation does not contain detectable amounts of cerium oxide.

[0029] "Photolytically degradable organic compound" refers to an organic compound that undergoes photolysis over a period of time. In some embodiments, a photolytically degradable organic compound exhibits a measurable decrease in concentration after exposure to light compared to the same organic compound that has not been exposed to light (i.e., left in the dark). The light can be ultraviolet light, visible light, or a combination thereof.

[0030] "Titanium dioxide" or "TiO2" may be in any form. In some embodiments, TiO2 includes brookite, rutile, anatase, or a combination of two or more thereof. In some embodiments, TiO2 includes rutile and anatase. In some embodiments, TiO2 is in rutile. In some embodiments, TiO2 is in anatase. In some embodiments, the weight percent of rutile and anatase in TiO2 is about 70:30 to about 95:5. In some embodiments, the weight percent of rutile and anatase in TiO2 is about 75:25 to about 95:5. In some embodiments, the weight percent of rutile and anatase in TiO2 is about 80:20 to about 90:10. In some embodiments, the weight percent of rutile and anatase in TiO2 is about 85:15.

[0031] "P25" refers to TiO2 containing 85 wt% rutile TiO2 and 15 wt% anatase TiO2.

[0032] "R706" refers to Ti-Pure R706 material, which is known in the art to include a rutile TiO2 core having a diameter of 290 nm and an aluminosilicate shell that acts as an overcoat for the core, the shell being approximately 5-10 nm thick. One function of this overcoat is to reduce the photocatalytic activity of the R706 pigment. Those skilled in the art will appreciate that R706 is a standard commercially available pigment commonly used in paints and coatings.

[0033] "Mixing time" refers to the situation when a volume of a first solution is added to a second solution. Mixing time is the time it takes to add the entire volume of a first solution to a second solution when forming a mixture of the two solutions.

[0034] "Direct" refers to a delay in adding a freshly prepared first mixture to another solid or mixture. In this context, "direct" means that the first mixture is added to another solid or mixture immediately after synthesis of the first mixture, with a typical delay of less than 1 minute, or 40 seconds, or 30 seconds after synthesis of the first mixture.

[0035] The term "UV protection agent" as used in this disclosure refers to either a UV-filtering agent or an agent that consumes reactive oxygen species (ROS) by catalytically or stoichiometrically reacting with ROS.

[0036] "UV filtering agents" refer to organic or inorganic compounds that absorb ultraviolet radiation.

[0037] The term "UV radiation" or "ultraviolet rays" as used in this disclosure refers to ultraviolet rays capable of photodecomposing organic molecules. Ultraviolet rays include blue light in the wavelength range of 400 nm to 495 nm, UVA rays (typically having a wavelength of 400 nm to 315 nm), and UVB rays (315 nm to 280 nm).

[0038] The term "reactive oxygen species" or "ROS" refers to oxidizing molecules that are synthesized by exposing a mixture of water and oxygen to UV light. Thus, ROS are synthesized by exposing skin (containing water) to UV radiation in the presence of air (containing oxygen) (see Journal of Investigative Dermatology 2014, 134, 1512-1518).

[0039] The term "photocatalyst" refers to an agent that can accelerate the rate of ROS production by exposing a mixture of water and oxygen to ultraviolet light (see ACS Nano 2012, 6, 5164-5173). Many photocatalysts include metal oxides such as, but not limited to, ZnO (see Journal of Photochemistry and Photobiology A: Chemistry 2005, 174, 82-87) and TiO2 (see Ind. Eng. Chem. Res. 2014, 53, 189-197).

[0040] The term "sunburn" is used in this disclosure according to its generally accepted meaning in the art. Skin tanning is understood to result from excessive exposure to ultraviolet (UV) radiation. In one embodiment, the sunburn is a first degree burn. In some other embodiments, the patient in need of treatment has a sunburn that is a superficial (reach down to the papillary dermis) or deep (reach down to the reticular dermis) second degree burn. In yet other embodiments, the patient in need of treatment has a sunburn that is a third degree burn. In some other embodiments, the patient has a sunburn that is a fourth degree burn. Thus, in some embodiments, the sunburn is an acute sunburn. The term "acute sunburn" is used according to its generally understood meaning in the art. Exemplary burn symptoms include, but are not limited to, erythema (redness), pain, edema (swelling), itching, peeling, rash, blisters, warmth, nausea, headache, and fever.

[0041] An "effective amount" or a "therapeutically effective amount" of a compound refers to a therapeutically effective amount of a compound administered to a subject. It refers to the amount of a compound sufficient to produce a beneficial effect on the body.

[0042] For the purposes of this disclosure, the terms "composition" and "formulation" are used interchangeably.

[0043] The term "lotion" in the context of the present invention refers to, but is not limited to, cosmetics and cosmetic foundations, sunscreens, sunscreen creams, sun care products, and personal care products.

[0044] Cerium(III) Carbonate The present disclosure provides cerium(III) carbonate of formula Ce2(CO3)3·xH2O, where x is zero or a positive number. In some embodiments, x is 0, 1, 2, 3, 4, 5, or 6. In some embodiments, x is 0. In some embodiments, x is 1. In some embodiments, x is 2. In some embodiments, x is 3. In some embodiments, x is 4. In some embodiments, x is 5. In some embodiments, x is 6. In some embodiments, the cerium(III) carbonate is substantially free of cerium(IV). In some embodiments, the cerium(III) carbonate is substantially free of a cerium oxide phase. In some embodiments, the cerium(III) carbonate is substantially free of cerium(IV) and substantially free of a cerium oxide phase. In some embodiments, the cerium(III) carbonate releases at least 27.6 wt% CO2 during mass analysis, when normalized to the dry weight of the hot cerium(III) carbonate. In some embodiments, x is 6. In some embodiments, the cerium(III) carbonate is white in appearance. In some embodiments, thermogravimetric analysis is used to determine whether the cerium(III) carbonate is substantially free of a cerium oxide phase, because such cerium(III) carbonate releases a higher wt% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate, compared to cerium(III) carbonate that also contains a cerium oxide phase. The amount of CO2 released upon heating a sample of cerium(III) carbonate is measured by thermogravimetric analysis. In some embodiments, the cerium(III) carbonate releases at least 27.7 wt% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 27.8 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 27.9 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 28 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate.In some embodiments, the cerium (III) carbonate releases at least 28.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium carbonate releases at least 28.6 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium (III) carbonate releases at least 28.7 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium (III) carbonate releases at least 28.8 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium (III) carbonate releases at least 28.9 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 29 wt.% CO during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate has a peak at 1410 cm as measured by ATR-FTIR. -1 and 1468cm -1 In some embodiments, the cerium(III) carbonate has a peak intensity ratio of 1410 cm to 1410 cm when measured by ATR-FTIR. -1 and 1468cm -1 In some embodiments, the cerium(III) carbonate has a peak intensity ratio of 1410 cm to 1410 cm when measured by ATR-FTIR. -1 and 1468cm -1 In some embodiments, the cerium(III) carbonate has a peak intensity ratio of 1410 cm to 1410 cm when measured by ATR-FTIR. -1 and 1468cm -1 The ratio of the peak intensities at 1410 cm to 1410 cm is approximately 0.95 or less. -1 and 1468cm -1is about 0.9 or less. In some embodiments, the cerium(III) carbonate comprises at least 6.6 wt% carbon and at least 1.5 wt% hydrogen as measured by CHN analysis. In some embodiments, the cerium(III) carbonate comprises at least 6.6 wt% carbon and at least 1.6 wt% hydrogen as measured by CHN analysis. In some embodiments, the cerium(III) carbonate comprises at least 6.6 wt% carbon and at least 1.7 wt% hydrogen as measured by CHN analysis. In some embodiments, the cerium(III) carbonate comprises at least 6.7 wt% carbon and at least 1.7 wt% hydrogen as measured by CHN analysis. In some embodiments, the cerium(III) carbonate comprises about 6.7 wt% carbon and about 1.76 wt% hydrogen as measured by CHN analysis. In some embodiments, the present disclosure provides cerium(III) carbonate as described herein and an organic compound susceptible to photolysis. In some embodiments, the present disclosure provides a method for inhibiting photolysis of an organic compound by combining cerium(III) carbonate as described herein with an organic compound susceptible to photolysis.

[0045] In one embodiment, the cerium(III) carbonate has the formula Ce2(CO3)3·xH2O, where x is zero or a positive number, and the cerium(III) carbonate releases at least 27.6 wt.% CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium(III) carbonate. In one embodiment, the cerium(III) carbonate is (a) substantially free of cerium(IV), (b) substantially free of cerium oxide phases, or (c) substantially free of cerium(IV) and substantially free of cerium oxide phases. In one embodiment, the cerium(III) carbonate is white in appearance. In one embodiment, the cerium(III) carbonate has the formula Ce2(CO3)3·xH2O, where x is 0, 1, 2, 3, 4, 5, or 6. In one embodiment, the cerium(III) carbonate has the formula Ce2(CO3)3·xH2O, where x is 4. In one embodiment, the cerium(III) carbonate has the formula Ce2(CO3)3·xH2O, where x is 0 or a positive number, and the cerium(III) carbonate releases at least 28 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate. In one embodiment, the cerium(III) carbonate is (a) substantially free of cerium(IV), (b) substantially free of cerium oxide phases, or (c) substantially free of cerium(IV) and substantially free of cerium oxide phases, and the cerium(III) carbonate releases at least 28 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate. In one embodiment, the cerium (III) carbonate has the formula Ce2(CO3)3·xH2O, where x is 0 or a positive number, and the cerium (III) carbonate releases at least 28.5 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate.In one embodiment, the cerium(III) carbonate is (a) substantially free of cerium(IV), (b) substantially free of cerium oxide phases, or (c) substantially free of cerium(IV) and substantially free of cerium oxide phases, and the cerium(III) carbonate releases at least 28.5 wt.% CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate. In one embodiment, the cerium(III) carbonate has the formula Ce2(CO3)3·xH2O, where x is 0 or a positive number, and the cerium(III) carbonate releases at least 29 wt.% CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate. In one embodiment, the cerium(III) carbonate is (a) substantially free of cerium(IV); (b) substantially free of cerium oxide phases; or (c) substantially free of cerium(IV) and substantially free of cerium oxide phases, and the cerium(III) carbonate releases at least 29 wt.% CO during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate.

[0046] Formulation: Cerium(III) carbonate and organic compounds The present disclosure provides a formulation comprising cerium(III) carbonate and an organic compound susceptible to photodecomposition. In some embodiments, the cerium(III) carbonate source material is Ce2(CO3)3·xH2O, where x is zero or a positive number. In some embodiments, the positive number is an integer between 1 and 6. In some embodiments, the cerium carbonate source material is Ce2(CO3)3·4H2O. In some embodiments, the cerium(III) carbonate source material is substantially free of cerium(IV) and / or substantially free of cerium oxide phases. In some embodiments, the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that releases at least 21.9 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate source material. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 27.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 27.6 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate source material releases at least 28.0 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some aspects, the cerium (III) carbonate source material releases at least 28.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 29.0 wt% CO2 during thermogravimetric analysis, as normalized to the dry mass of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that includes at least 5.7 wt% carbon and at least 0.9 wt% hydrogen, as measured by CHN analysis. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that includes at least 6.5 wt% carbon and at least 1.45 wt% hydrogen, as measured by CHN analysis.In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that contains about 6.7 wt. % carbon and about 1.76 wt. % hydrogen as measured by CHN analysis. In some embodiments, the cerium (III) carbonate source material has a peak at 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate source material has an intensity of about 1.3 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate source material has an intensity of about 1.0 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate source material has an intensity of about 0.9 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium (III) carbonate source material is white in color. In some embodiments, the cerium (III) carbonate source material is substantially insoluble in water.

[0047] In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.05 wt% to about 20 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.1 wt% to about 15 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 1 wt% to about 10 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 1 wt% to about 5 wt% based on the total weight of the formulation.

[0048] In the formulations described herein, the photodegradable organic compound is present in an amount of about 1 wt% to about 75 wt% of the total mass of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 1 wt% to about 50 wt% of the total mass of the formulation. The photodegradable organic compound is present in an amount of about 1 wt% to about 40 wt% of the total mass of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 3 wt% to about 35 wt% of the total mass of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 5 wt% to about 30 wt% of the total mass of the formulation.

[0049] In the formulations described herein, the cerium compound has a molar ratio of cerium(III) to cerium(IV) of greater than 1, as measured by X-ray photoelectron spectroscopy (XPS), and therefore most preferably includes ligands that stabilize cerium in the (III) oxidation state rather than the (IV) oxidation state. Such ligands are known in the art to include phosphate and carbonate ligands.

[0050] The present disclosure provides a formulation comprising cerium(III) carbonate and an organic compound susceptible to photodecomposition. In some embodiments, the cerium(III) carbonate is Ce2(CO3)3·xH2O, where x is zero or a positive number. In some embodiments, the positive number is an integer between 1 and 6. In some embodiments, the cerium(III) carbonate is Ce2(CO3)3·4H2O. In some embodiments, the cerium(III) carbonate source material is substantially free of cerium(IV) and / or substantially free of cerium oxide phases. In some embodiments, the cerium(III) carbonate releases at least 21.9 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 27.5 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium (III) carbonate releases at least 27.6 wt.% CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium (III) carbonate releases at least 28.0 wt.% CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium carbonate releases at least 28.5 wt.% CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium carbonate releases at least 29.0 wt.% CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium (III) carbonate contains at least 5.7 wt.% carbon and at least 0.9 wt.% hydrogen, as measured by CHN analysis. In some embodiments, the cerium (III) carbonate contains at least 6.5 wt.% carbon and at least 1.45 wt.% hydrogen as measured by CHN analysis. In some embodiments, the cerium (III) carbonate contains about 6.7 wt.% carbon and about 1.76 wt.% hydrogen as measured by CHN analysis. In some embodiments, the cerium (III) carbonate contains at least one fluorine atom at 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1In some embodiments, the cerium(III) carbonate has an intensity of about 1.3 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate has an intensity of about 1.0 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In an embodiment, the intensity is about 0.9 or less in a band in the range of 1410 cm -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate is substantially insoluble in water.

[0051] In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.005 wt% to about 20 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.01 wt% to about 15 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.1 wt% to about 10 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.1 wt% to about 5 wt% based on the total weight of the formulation.

[0052] In the formulations described herein, the photodegradable organic compound is present in an amount of about 1 wt% to about 75 wt% of the total mass of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 1 wt% to about 50 wt% of the total mass of the formulation. The photodegradable organic compound is present in an amount of about 1 wt% to about 40 wt% of the total mass of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 3 wt% to about 35 wt% of the total mass of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 5 wt% to about 30 wt% of the total mass of the formulation.

[0053] In the formulations described herein, the cerium compound has a molar ratio of cerium(III) to cerium(IV) of greater than 1, as measured by X-ray photoelectron spectroscopy (XPS), and therefore most preferably includes ligands that stabilize cerium in the (III) oxidation state rather than the (IV) oxidation state. Such ligands are known in the art to include phosphate and carbonate ligands.

[0054] In one embodiment, the formulation comprises cerium (III) carbonate and an organic compound susceptible to photodecomposition. In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 21.9 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 27.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 28.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 29.0 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium(III) carbonate is (a) substantially free of cerium(IV), (b) substantially free of cerium oxide phases, or (c) substantially free of cerium(IV) and substantially free of cerium oxide phases. In one embodiment, the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that is white in color. In one embodiment, the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that is substantially insoluble in water.

[0055] In one embodiment, the formulation comprising cerium(III) carbonate and an organic compound susceptible to photodecomposition further comprises a photocatalytically active pigment. In one embodiment, the photocatalytically active pigment comprises titanium dioxide. In one embodiment, the formulation comprises from about 1 wt% to about 20 wt% cerium(III) carbonate relative to the amount of photocatalytically active pigment. In one embodiment, the formulation comprises from about 1 wt% to about 10 wt% cerium carbonate relative to the amount of photocatalytically active pigment. In one embodiment, the formulation comprises from about 1 wt% to about 5 wt% cerium carbonate relative to the amount of photocatalytically active pigment. In one embodiment, the formulation comprises about 2 wt% cerium(III) carbonate relative to the amount of photocatalytically active pigment. In one embodiment, the cerium(III) carbonate is in the same phase as the photocatalytically active pigment. In one embodiment, the cerium(III) carbonate is in a different phase from the photocatalytically active pigment. In one embodiment, the molar ratio of cerium(III) to cerium(IV) in the formulation is greater than 1.0.

[0056] Formulation: Cerium carbonate, organic compounds, photocatalytically active pigments The present disclosure provides a formulation comprising cerium(III) carbonate, an organic compound susceptible to photolysis, and a photocatalytically active pigment. In some embodiments, the formulation may optionally further comprise a solvent, such as water. In some embodiments, the formulation may optionally further comprise one or more dyes. In some embodiments, the cerium(III) carbonate source material is Ce2(CO3)3·xH2O, where x is zero or a positive number. In some embodiments, the positive number is an integer between 1 and 6. In some embodiments, the cerium(III) carbonate source material is Ce2(CO3)3·4H2O. In some embodiments, the cerium(III) carbonate source material is substantially free of cerium(IV) and / or substantially free of cerium oxide phases. In some embodiments, the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that releases at least 21.9 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate source material. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 27.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 27.6 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some aspects, the cerium (III) carbonate source material releases at least 28.0 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some aspects, the cerium (III) carbonate source material releases at least 28.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 29.0 wt.% CO during thermogravimetric analysis, as normalized to the dry mass of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that includes at least 5.7 wt.% carbon and at least 0.9 wt.% hydrogen, as measured by CHN analysis.In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that includes at least 6.5 wt% carbon and at least 1.45 wt% hydrogen as measured by CHN analysis. In some embodiments, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that includes about 6.7 wt% carbon and about 1.76 wt% hydrogen as measured by CHN analysis. In some embodiments, the cerium (III) carbonate source material has a peak at 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate source material has an intensity of about 1.3 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate source material has an intensity of about 1.0 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate source material has an intensity of about 0.9 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium (III) carbonate source material is white. In some embodiments, the cerium (III) carbonate source material is substantially insoluble in water. In some embodiments, the photocatalytically active pigment comprises titanium dioxide.

[0057] In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.005 wt% to about 20 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.01 wt% to about 15 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.1 wt% to about 10 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.1 wt% to about 5 wt% based on the total weight of the formulation.

[0058] In some embodiments, the cerium (III) carbonate is present in an amount of about 0.5 wt% to about 20 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 15 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 10 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 5 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 4 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 3 wt% based on the weight of the photocatalytically active pigment. In the formulations described in this disclosure, cerium(III) carbonate is present in an amount of about 2 wt % based on the mass of the photocatalytically active pigment.

[0059] In the formulations described herein, the photodegradable organic compound is present in an amount of about 1 wt% to about 75 wt% based on the total weight of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 1 wt% to about 50 wt% based on the total weight of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 1 wt% to about 40 wt% based on the total weight of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 3 wt% to about 35 wt% based on the total weight of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 5 wt% to about 30 wt% based on the total weight of the formulation.

[0060] The formulation may optionally include water. In the formulations described herein, water is present in an amount of about 1 wt% to about 70 wt% of the total weight of the formulation. In some embodiments, water is present in an amount of about 1 wt% to about 65 wt% of the total weight of the formulation. In some embodiments, water is present in an amount of about 5 wt% to about 60 wt% of the total weight of the formulation. In some embodiments, water is present in an amount of about 10 wt% to about 60 wt% of the total weight of the formulation.

[0061] The formulation may optionally include one or more dyes. In the formulations described herein, the dye is optionally present in the formulation in an amount of about 0.1 wt% to about 50 wt% of the total weight of the formulation. In some embodiments, the dye is present in the formulation in an amount of about 0.1 wt% to about 40 wt% of the total weight of the formulation. In some embodiments, the dye is present in the formulation in an amount of about 1 wt% to about 35 wt% of the total weight of the formulation. In some embodiments, the dye is present in the formulation in an amount of about 5 wt% to about 30 wt% of the total weight of the formulation.

[0062] In the formulations described herein, the cerium compound has a molar ratio of cerium(III) to cerium(IV) of greater than 1, as measured by X-ray photoelectron spectroscopy (XPS), and therefore most preferably includes ligands that stabilize cerium in a post(III) oxidation state rather than a (IV) oxidation state.

[0063] In some embodiments, the cerium(III) carbonate is in the same phase as the photocatalytically active pigment. In some aspects, the cerium(III) carbonate precipitates in the presence of the photocatalytically active pigment and / or is in close proximity to the photocatalytically active pigment. In other words, the cerium(III) carbonate particles are bonded to or in intimate mechanical contact with the photocatalytically active pigment particles. In some aspects, the cerium(III) carbonate contacts the surface of the photocatalytically active pigment. In some aspects, the cerium(III) carbonate is deposited or precipitated in the presence of the photocatalytically active pigment. In some aspects, the cerium compound undergoes macroscale precipitation onto the photocatalytically active pigment.

[0064] In some embodiments, the cerium(III) carbonate is in a separate phase from the photocatalytically active pigment. In some embodiments, the cerium(III) carbonate is not precipitated on the photocatalytically active pigment and / or is not in close proximity to the photocatalytically active pigment. In other words, the cerium(III) carbonate particles are not bonded to or in intimate mechanical contact with the photocatalytically active pigment particles. In some embodiments, the cerium(III) carbonate is not in contact with the surface of the photocatalytically active pigment. In some embodiments, the cerium(III) carbonate is not deposited or precipitated on the photocatalytically active pigment. In some embodiments, the cerium compound does not undergo macroscopic phase separation and remains uniformly dispersed in the formulation (which is a fluid) or composition, which may be either wet or dry.

[0065] The present disclosure provides a formulation comprising cerium(III) carbonate, an organic compound susceptible to photolysis, and a photocatalytically active pigment. In some embodiments, the formulation may optionally further comprise a solvent, such as water. In some embodiments, the formulation may optionally further comprise one or more dyes. In some embodiments, the cerium(III) carbonate is Ce2(CO3)3·xH2O, where x is zero or a positive number. In some embodiments, the positive number is an integer between 1 and 6. In some embodiments, the cerium(III) carbonate source material is substantially free of cerium(IV) and / or substantially free of a cerium oxide phase. In some embodiments, the cerium(III) carbonate is Ce2(CO3)3·4H2O. In some embodiments, the cerium(III) carbonate releases at least 21.9 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate source material. In some embodiments, the cerium(III) carbonate releases at least 27.5 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium carbonate source material. In some embodiments, the cerium(III) carbonate releases at least 27.6 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium carbonate source material. In some aspects, the cerium(III) carbonate releases at least 28.0 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some aspects, the cerium(III) carbonate releases at least 28.5 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate. In some embodiments, the cerium(III) carbonate releases at least 29.0 wt.% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium carbonate source material. In some embodiments, the cerium(III) carbonate contains at least 5.7 wt.% carbon and at least 0.9 wt.% hydrogen as determined by CHN analysis. In some embodiments, the cerium(III) carbonate contains at least 6.5 wt.% carbon and at least 1.45 wt.% hydrogen as determined by CHN analysis.In some embodiments, the cerium (III) carbonate contains about 6.7 wt. % carbon and about 1.76 wt. % hydrogen as measured by CHN analysis. In some embodiments, the cerium (III) carbonate contains about 1.4 wt. % carbon and about 1.76 wt. % hydrogen as measured by ATR-FTIR analysis. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate has an intensity of about 1.3 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate has an intensity of about 1.0 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, cerium(III) carbonate has an intensity of about 0.9 or less in the band in the range of 1410 cm to 1420 cm as measured by ATR-FTIR. -1 ~1468cm -1 In some embodiments, the cerium(III) carbonate is white. In some embodiments, the cerium(III) carbonate is substantially insoluble in water. In some embodiments, the photocatalytically active pigment comprises titanium dioxide.

[0066] In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.005 wt% to about 20 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.01 wt% to about 15 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.1 wt% to about 10 wt% based on the total weight of the formulation. In the formulations described herein, cerium(III) carbonate is present in an amount of about 0.1 wt% to about 5 wt% based on the total weight of the formulation.

[0067] In some embodiments, the cerium (III) carbonate is present in an amount of about 0.5 wt% to about 20 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 15 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 10 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 5 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 4 wt% based on the weight of the photocatalytically active pigment. In the formulations described herein, the cerium (III) carbonate is present in an amount of about 1 wt% to about 3 wt% based on the weight of the photocatalytically active pigment. In the formulations described in this disclosure, cerium(III) carbonate is present in an amount of about 2 wt % based on the mass of the photocatalytically active pigment.

[0068] In the formulations described herein, the photodegradable organic compound is present in an amount of about 1 wt% to about 75 wt% based on the total weight of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 1 wt% to about 50 wt% based on the total weight of the formulation. The photodegradable organic compound is present in an amount of about 1 wt% to about 40 wt% based on the total weight of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 3 wt% to about 35 wt% based on the total weight of the formulation. In some embodiments, the photodegradable organic compound is present in an amount of about 5 wt% to about 30 wt% based on the total weight of the formulation.

[0069] In the formulations described herein, the cerium compound has a molar ratio of cerium(III) to cerium(IV) of greater than 1, as measured by X-ray photoelectron spectroscopy (XPS), and therefore most preferably includes ligands that stabilize cerium in the (III) oxidation state rather than the (IV) oxidation state.

[0070] In some embodiments, the cerium(III) carbonate is in the same phase as the photocatalytically active pigment. In some embodiments, the cerium(III) carbonate precipitates in the presence of the photocatalytically active pigment and / or is in close proximity to the photocatalytically active pigment. In other words, the cerium(III) carbonate particles are bound to or form a coordination compound with the photocatalytically active pigment. In some embodiments, the cerium(III) carbonate contacts the photocatalytically active pigment. In some embodiments, the cerium(III) carbonate is deposited or precipitated in the presence of the photocatalytically active pigment. In some embodiments, the cerium compound undergoes macroscale precipitation onto the photocatalytically active pigment.

[0071] In some embodiments, the cerium(III) carbonate is in a separate phase from the photocatalytically active pigment. In some embodiments, the cerium(III) carbonate is not precipitated on the photocatalytically active pigment and / or is not in close proximity to the photocatalytically active pigment. In other words, the cerium(III) carbonate particles are not bonded to or in intimate mechanical contact with the photocatalytically active pigment particles. In some embodiments, the cerium(III) carbonate does not contact the surface of the photocatalytically active pigment. In some embodiments, the cerium(III) carbonate does not deposit or precipitate on the photocatalytically active pigment. In some embodiments, the cerium compound does not undergo macroscopic phase separation and remains uniformly dispersed in the formulation (which is a fluid) or composition, which is either wet or dry.

[0072] Formulation: Cerium carbonate, pigments, and / or dyes In one embodiment, the present invention relates to a formulation comprising cerium(III) carbonate and a pigment or dye or a combination thereof. In one embodiment, the formulation comprises a solvent. Exemplary solvents are described elsewhere in this disclosure.

[0073] The cerium (III) carbonate can be any cerium (III) carbonate described elsewhere in this disclosure and having the properties described elsewhere in this disclosure. In one embodiment, the cerium (III) carbonate does not contain electrostatically attached carbonate. In one embodiment, the cerium (III) carbonate releases at least 27.5 wt. % CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium (III) carbonate. In one embodiment, the cerium (III) carbonate is Ce2(CO3)3·4H2O or Ce2(CO3)3·6H2O.

[0074] The pigment may be any pigment described elsewhere in this disclosure, hi one embodiment, the pigment is titanium dioxide.

[0075] The dye may be any of the dyes described elsewhere in this disclosure. In one embodiment, the dye is selected from the group consisting of iron oxides, carbon black, cadmium sulfide, toluidene red, chrome orange, chrome yellow, chrome green, polyazaindacenes, coumarins, lanthanide complexes, hydrocarbon and substituted hydrocarbon dyes, polycyclic aromatic hydrocarbons, scintillation dyes, aryl and heteroaryl substituted polyolefins, carbocyanine dyes, phthalocyanine dyes and pigments, oxazine dyes, carbostyril dyes, porphyrin dyes, acridine dyes, anthraquinone dyes, anthrapyridone dyes, naphthalimide dyes, benzimidazole derivatives, arylmethane dyes, azo dyes, diazonium dyes, nitro dyes, quinoneimine dyes, tetrazolium dyes, thiazole dyes, perylene dyes, perinone dyes, bis-benzoxazolylthiophenes, xanthene dyes, indigoid dyes, chromone dyes, flavone dyes, thiazine dyes, and combinations thereof. In one embodiment, the dye is selected from the group consisting of iron oxide, carbon black, cadmium sulfide, toluidene red, chrome orange, chrome yellow, chrome green, and combinations thereof, hi one embodiment, the dye is methylene blue or congo red.

[0076] In one embodiment, cerium (III) carbonate is present in an amount of about 0.005 wt% to about 80 wt% based on the total weight of the formulation. In one embodiment, cerium (III) carbonate is present in an amount of about 0.005 wt% to about 70 wt% based on the total weight of the formulation. In one embodiment, cerium (III) carbonate is present in an amount of about 0.005 wt% to about 60 wt% based on the total weight of the formulation. In one embodiment, cerium (III) carbonate is present in an amount of about 0.005 wt% to about 50 wt% based on the total weight of the formulation. In one embodiment, cerium (III) carbonate is present in an amount of about 0.005 wt% to about 40 wt% based on the total weight of the formulation. In one embodiment, cerium (III) carbonate is present in an amount of about 0.005 wt% to about 30 wt% based on the total weight of the formulation. In one embodiment, cerium(III) carbonate is present in an amount of about 0.005 wt% to about 20 wt% based on the total weight of the formulation. In one embodiment, cerium(III) carbonate is present in an amount of about 0.01 wt% to about 15 wt% based on the total weight of the formulation. In one embodiment, cerium(III) carbonate is present in an amount of about 0.1 wt% to about 10 wt% based on the total weight of the formulation. In one embodiment, cerium(III) carbonate is present in an amount of about 0.1 wt% to about 5 wt% based on the total weight of the formulation.

[0077] In one embodiment, the dye is present in an amount of about 0.1 wt% to about 90 wt% of the total weight of the formulation. In one embodiment, the dye is present in an amount of about 0.1 wt% to about 80 wt% of the total weight of the formulation. In one embodiment, the dye is present in an amount of about 0.1 wt% to about 70 wt% of the total weight of the formulation. In one embodiment, the dye is present in an amount of about 0.1 wt% to about 60 wt% of the total weight of the formulation. In one embodiment, the dye is present in an amount of about 0.1 wt% to about 50 wt% of the total weight of the formulation. In one embodiment, the dye is present in an amount of about 0.1 wt% to about 40 wt% of the total weight of the formulation. In one embodiment, the dye is present in an amount of about 1 wt% to about 35 wt% of the total weight of the formulation. In one embodiment, the dye is present in an amount of about 5 wt% to about 30 wt% of the total weight of the formulation.

[0078] Formulation: Cerium Carbonate and UV Protectant The present disclosure provides a formulation comprising cerium(III) carbonate and one or more UV protection agents. In one embodiment, the UV protection agent is a UV filtering agent.

[0079] In one embodiment, the formulation comprising cerium carbonate and one or more UV protection agents comprises cerium(III) carbonate obtained from a cerium carbonate source material. In one embodiment, the UV protection agent is a UV filtering agent. In some embodiments, the cerium(III) carbonate source material is Ce2(CO3)3·xH2O, where x is zero or a positive number. In some embodiments, the positive number is an integer from 1 to 6. In some embodiments, the cerium carbonate source material is Ce2(CO3)3·4H2O. In one embodiment, the cerium carbonate source material is Ce2(CO3)3·6H2O. In some embodiments, the cerium(III) carbonate source material is substantially free of cerium(IV) and / or substantially free of a cerium oxide phase.

[0080] In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 21.9 wt. % CO2 during thermogravimetric analysis, as normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 27.5 wt. % CO2 during thermogravimetric analysis, as normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material that releases at least 27.6 wt. % CO2 during thermogravimetric analysis, as normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate source material releases at least 28.0 wt. % CO2 during thermogravimetric analysis, as normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium(III) carbonate source material releases at least 28.5 wt.% CO during thermogravimetric analysis, as normalized to the dry weight of the cerium(III) carbonate source material. In one embodiment, the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that releases at least 29.0 wt.% CO during thermogravimetric analysis, as normalized to the dry weight of the cerium(III) carbonate source material.

[0081] In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material comprising at least 5.7 wt% carbon and at least 0.9 wt% hydrogen as measured by CHN analysis. In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material comprising at least 6.5 wt% carbon and at least 1.45 wt% hydrogen as measured by CHN analysis. In one embodiment, the cerium (III) carbonate is obtained from a cerium (III) carbonate source material comprising about 6.7 wt% carbon and about 1.76 wt% hydrogen as measured by CHN analysis.

[0082] In one embodiment, the cerium (III) carbonate source material has a fluorine-containing cation exchange ratio (FIR) of 1410 cm as measured by ATR-FTIR.-1 ~1468cm -1 In one embodiment, the cerium(III) carbonate source material has an intensity of about 1.3 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In one embodiment, the cerium(III) carbonate source material has an intensity of about 1.0 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In one embodiment, the cerium(III) carbonate source material has an intensity of about 0.9 or less in the band in the range of 1410 cm as measured by ATR-FTIR. -1 ~1468cm -1 In one embodiment, the cerium (III) carbonate source material is white in color. In one embodiment, the cerium (III) carbonate source material is substantially insoluble in water.

[0083] In one embodiment, the cerium (III) carbonate is Ce2(CO3)3·xH2O, where x is zero or a positive number. In one embodiment, the positive number is an integer from 1 to 6. In one embodiment, the cerium (III) carbonate is Ce2(CO3)3·4H2O. In one embodiment, the cerium (III) carbonate is Ce2(CO3)3·6H2O.

[0084] In the formulations described herein, cerium (III) carbonate is present in an amount of about 0.05 wt% to about 50 wt% based on the total weight of the formulation. In the formulations described herein, cerium (III) carbonate is present in an amount of about 0.05 wt% to about 40 wt% based on the total weight of the formulation. In the formulations described herein, cerium (III) carbonate is present in an amount of about 0.05 wt% to about 30 wt% based on the total weight of the formulation. In the formulations described herein, cerium (III) carbonate is present in an amount of about 0.05 wt% to about 20 wt% based on the total weight of the formulation. In the formulations described herein, cerium (III) carbonate is present in an amount of about 0.1 wt% to about 15 wt% based on the total weight of the formulation. In the formulations described herein, cerium (III) carbonate is present in an amount of about 0.5 wt% to about 7 wt% based on the total weight of the formulation.

[0085] In one embodiment, the UV protection agent comprises one or more metal oxides. The metal oxide may be any metal oxide known to those skilled in the art to provide UV protection. Exemplary metal oxides include, but are not limited to, titanium dioxide, zinc oxide, cerium oxide, zirconium oxide, tungsten oxide, vanadium oxide, tin oxide, nickel oxide, copper oxide, molybdenum oxide, tungsten sulfide, cadmium sulfide, cadmium selenide, zinc sulfide, and combinations thereof. In one embodiment, the UV protection agent is zinc oxide. In one embodiment, the UV protection agent is titanium oxide. In one embodiment, the UV-protection agent is a combination of zinc oxide and titanium oxide. In one embodiment, the UV protection agent is a UV filtering agent.

[0086] In one embodiment, the UV protection agent comprises one or more metal oxides and one or more UV protection agents that are not metal oxides. The one or more UV protection agents that are not metal oxides can be any non-metal oxide UV protection agent known to one of skill in the art. Exemplary non-metal oxide UV protection agents include, but are not limited to, avobenzone, methyl anthranilate, ecamsule, octyl methoxycinnamate, homosalate, oxybenzone, sulisobenzone, PABA, padimate O, cinoxate, octyl salicylate, trolamine salicylate, octylcrylene, ensulizole, octyl triazone, enzacamene, amiloxate, dioxybenzone, mexoryl XL, tinosorb S, tinosorb M, neo heliopan AP, uvinul Aplus, UVAsorb HEB, and combinations thereof. In one embodiment, the UV protection agent is a UV filtering agent.

[0087] In the formulations described herein, the UV protection agent is present in an amount of about 0.1% w / w to 75% w / w of the total weight of the formulation. In the formulations described herein, the UV protection agent is present in an amount of about 0.1% w / w to 65% w / w of the total weight of the formulation. In the formulations described herein, the UV protection agent is present in an amount of about 0.1% w / w to 55% w / w of the total weight of the formulation. In the formulations described herein, the UV protection agent is present in an amount of about 0.1% w / w to 45% w / w of the total weight of the formulation. In the formulations described herein, the UV protection agent is present in an amount of about 1% w / w to 40% w / w of the total weight of the formulation. In one embodiment, the UV protection agent is a UV filtering agent.

[0088] In one embodiment, the formulation comprising cerium(III) carbonate and one or more UV protection agents is a topical lotion. In one embodiment, the UV protection agent is a UV filtering agent. In one embodiment, the lotion comprises water. In one embodiment, the lotion comprises a dispersion of colloids in water. In one embodiment, the lotion comprises an oil phase. In one embodiment, the oil phase forms an emulsion in water. In one embodiment, the lotion comprising an oil phase further comprises an emulsifier, a surfactant, and / or a thickener. In one embodiment, the emulsifier aids in mixing of the water and oil components. The colloids, emulsifiers, surfactants, and thickeners can be any colloids, emulsifiers, surfactants, and thickeners known to those skilled in the art. In one embodiment, the lotion comprising water further comprises other ingredients known to those skilled in the art.

[0089] In one embodiment, the lotion is a dry lotion that does not contain water. In one embodiment, the dry lotion includes titanium dioxide and / or zinc oxide. In one embodiment, the dry lotion includes other metal oxides. Exemplary metal oxides are disclosed elsewhere in this disclosure. In one embodiment, the metal oxide is iron oxide. Exemplary dry lotions include, but are not limited to, powder foundations, face powders, and other powder cosmetics. In one embodiment, the dry lotion includes one or more agents to aid in the adhesion of the powder to the skin. The one or more agents to aid in the adhesion of the powder to the skin can be any agent known to one of skill in the art.

[0090] Pigments and dyes Pigments are particulate solids that are incorporated into the formulations described in this disclosure. Pigments are materials that change the color of refracted, reflected or transmitted light as a result of wavelength-selective absorption. Instead of or in combination with pigments, the formulations may contain dyes.

[0091] Pigments can be classified as either natural or synthetic. Natural pigments include various clays, calcium carbonate, mica, silica, talc, graphite, etc., or combinations thereof. Examples of synthetic pigments are titanium dioxide and other titanium-based pigments, white lead, barium sulfate, calcium carbonate, lithopone, silica, talc, mica, clay, calcined clay, iron oxide, carbon black, cadmium sulfide, toluidene red, chrome orange, chrome yellow, chrome green, and so-called reactive pigments, which are polyvalent metal compounds such as lead silicochromate, zinc chromate, calcium zinc molybdate, barium metaborate, zinc oxide, zinc sulfide, etc., or combinations thereof.

[0092] Dyes may be used alone or in combination with pigments. Exemplary dyes include polyazaindacenes and / or coumarins, lanthanide complexes, hydrocarbon and substituted hydrocarbon dyes, polycyclic aromatic hydrocarbons, scintillation dyes (e.g., oxazoles and oxadiazoles), aryl and heteroaryl substituted polyolefins (C2-C8 olefin moieties), carbocyanine dyes, phthalocyanine dyes and pigments, oxazine dyes, carbostyril dyes, porphyrin dyes, acridine dyes, anthraquinone dyes, anthrapyridone dyes, naphthalimide dyes, benzimidazole derivatives, arylmethane dyes, azo dyes (e.g., Congo Red), diazonium dyes, nitro dyes, quinoneimine dyes, tetrazolium dyes, thiazole dyes, perylene dyes, perinone dyes, bisbenzoxazolylthiophenes (BBOT), xanthene dyes (e.g., thioxanthene dyes), indigoid dyes (e.g., thioindigoid dyes), chromone dyes, flavone dyes, thiazine dyes (e.g., methylene blue), as well as the luminescent tags described herein. Luminescent tags also include anti-Stokes shift dyes that absorb at near infrared wavelengths and emit at visible wavelengths.

[0093] solvent The formulations described in the present disclosure may include a solvent. The solvent may be water, an aqueous solvent (i.e., a solvent that is compatible with water), a solvent that is immiscible with water, or a combination thereof. Supercritical fluids and / or superheated fluids may also be used as solvents in some formulations. In some embodiments, the solvent is water. In some embodiments, the solvent is an aqueous solvent. In some embodiments, the solvent is liquid carbon dioxide. Solvents that can be combined with water to form a co-solvent are also possible.

[0094] The solvent can be a liquid aprotic polar solvent, a polar protic solvent, a non-polar solvent, or a combination thereof. In general, liquid aprotic polar solvents, such as propylene carbonate, ethylene carbonate, butyrolactone, acetonitrile, benzonitrile, nitromethane, nitrobenzene, sulfolane, dimethylformamide, N-methylpyrrolidone, or a combination thereof, are preferred for dissolving the template. Polar protic solvents, such as water, methanol, acetonitrile, nitromethane, ethanol, propanol, isopropanol, butanol, or a combination thereof, may also be used. Other non-polar solvents, such as benzene, toluene, methylene chloride, carbon tetrachloride, hexane, diethyl ether, tetrahydrofuran, or a combination thereof, may also be used for dissolving the template. Examples of preferred solvents are water, alcohols, acetone, or a combination thereof. The most preferred solvent is water.

[0095] Method for producing cerium(III) carbonate The present disclosure provides a method for producing cerium (III) carbonate by (i) mixing a carbonate salt with water to form a first solution, (ii) mixing a cerium (III) salt with water to form a second solution, (iii) mixing the first and second solutions to form a third solution having a pH of 9.2 or less, and (iv) centrifuging the third solution to form the cerium (III) carbonate described herein. In some embodiments, the third solution has a pH of about 9.0 to 9.2 or less. In some embodiments, the third solution has a pH of about 9.1. In some embodiments, the third solution has a pH of about 9.0. In some embodiments, a sufficiently short mixing time is required when mixing the first and second solutions to form the third solution to achieve these pH values. In some embodiments, the mixing time is about 4 minutes or less. In some embodiments, the mixing time is about 3 minutes or less. In some embodiments, the mixing time is about 2 minutes or less. In some embodiments, the mixing time is about 1 minute or less. In some embodiments, the mixing time is about 45 seconds or less. In some embodiments, the mixing time is about 30 seconds or less. In some embodiments, the mixing time is about 20 seconds or less. In some embodiments, the mixing time is about 15 seconds or less. In some embodiments, the mixing time is about 10 seconds or less. In some embodiments, the mixing time is about 10 seconds to about 90 seconds. In some embodiments, the mixing time is about 10 seconds to about 60 seconds. In some embodiments, the mixing time is about 15 seconds to about 60 seconds. In some embodiments, the mixing time is about 15 seconds to about 45 seconds. In some embodiments, the mixing time is about 15 seconds to about 30 seconds. In some embodiments, the mixing time is about 15 seconds to about 20 seconds. It has been unexpectedly discovered that when the pH is greater than a threshold value around 9.2, or when the mixing time is greater than that described in the present disclosure (e.g., 1 minute or longer), the resulting cerium (III) carbonate is not white, but yellowish due to the presence of cerium (IV) species. In some embodiments, the cerium (III) carbonate used in the methods disclosed herein is a cerium (III) carbonate source material as described in detail in the present disclosure. In some embodiments, the cerium (III) carbonate is Ce2(CO3)3·4H2O. In some embodiments, the carbonate is a solid.In some embodiments, the carbonate salt is ammonium carbonate, aluminum carbonate, sodium carbonate, potassium carbonate, bicarbonate, etc. In some embodiments, the cerium(III) salt is ammonium cerium(III) nitrate, ammonium cerium(III) nitrate tetrahydrate, cerium(III) bromide, cerium(III) bromide hydrate, cerium(III) chloride, cerium(III) chloride heptahydrate, cerium(III) fluoride, cerium(III) iodide, cerium(III) nitrate, cerium(III) nitrate hexahydrate, cerium(III) oxalate hydrate, cerium(III) sulfate, cerium(III) sulfate hydrate, cerium(III) sulfate octahydrate, etc. The amount of each component to be used in the present method can be determined by one of skill in the art with reference to the examples of the present disclosure.

[0096] The present disclosure provides a method for producing cerium (III) carbonate by (i) mixing ammonium carbonate and cerium (III) ammonium nitrate tetrahydrate to form a first solution, (ii) washing the first solution with water, and (iii) centrifuging to recover the cerium (III) carbonate from the suspension. In some embodiments, the cerium (III) carbonate is Ce2(CO3)3·4H2O. In some embodiments, the cerium (III) carbonate is a cerium (III) carbonate source material as described in detail in the present disclosure. In some embodiments, the cerium (III) carbonate releases at least 28.0 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium carbonate releases at least 28.5 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium carbonate releases at least 29.0 wt% CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium carbonate source material. The amount of each component used in the present method can be determined by one of skill in the art with reference to the examples of the present disclosure.

[0097] The present disclosure provides a method for producing cerium(III) carbonate by (i) mixing ammonium carbonate with water to form a first solution, (ii) mixing ammonium cerium(III) nitrate tetrahydrate with water to form a second solution, (iii) mixing the first and second solutions to form a third solution having a pH of 9.2 or less, and (iv) centrifuging the third solution to form the cerium(III) carbonate described herein. In some embodiments, the third solution has a pH of about 9.0 to 9.2 or less. In some embodiments, the third solution has a pH of about 9.1. In some embodiments, the third solution has a pH of about 9.0. In some embodiments, a sufficiently short mixing time is required when mixing the first and second solutions to form the third solution to achieve these pH values. In some embodiments, the mixing time is about 4 minutes or less. In some embodiments, the mixing time is about 3 minutes or less. In some embodiments, the mixing time is about 2 minutes or less. In some embodiments, the mixing time is about 1 minute or less. In some embodiments, the mixing time is about 45 seconds or less. In some embodiments, the mixing time is about 30 seconds or less. In some embodiments, the mixing time is about 20 seconds or less. In some embodiments, the mixing time is about 15 seconds or less. In some embodiments, the mixing time is about 10 seconds or less. In some embodiments, the mixing time is about 10 seconds to about 90 seconds. In some embodiments, the mixing time is about 10 seconds to about 60 seconds. In some embodiments, the mixing time is about 15 seconds to about 60 seconds. In some embodiments, the mixing time is about 15 seconds to about 60 seconds. In some embodiments, the mixing time is about 15 seconds to about 45 seconds. In some embodiments, the mixing time is about 15 seconds to about 30 seconds. In some embodiments, the mixing time is about 15 seconds to about 20 seconds. In some embodiments, the cerium (III) carbonate releases at least 28.5 wt. % CO during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium carbonate releases at least 29.0 wt. % CO during thermogravimetric analysis, normalized to the dry weight of the cerium carbonate source material. In some embodiments, the cerium (III) carbonate is Ce2(CO3)3·4H2O. In some embodiments, the cerium (III) carbonate is a cerium (III) carbonate source material as described in detail herein.The amount of each component to be used in the present method can be determined by one of skill in the art with reference to the examples of the present disclosure.

[0098] In some embodiments of the methods described herein, step (iii) comprises vigorously mixing the first and second solutions for about 5 minutes to about 2 hours, or about 30 minutes to about 90 minutes, or about 45 minutes to about 75 minutes; or about 60 minutes. In some embodiments, step (iv) comprises centrifuging the third solution at about 5,000 rpm to about 30,000 rpm for about 1 minute to about 30 minutes at a temperature of about 5° C. to about 30° C. In some embodiments, step (iv) comprises centrifuging the third solution at about 10,000 rpm to about 20,000 rpm for about 1 minute to about 5 minutes at a temperature of about 10° C. to about 20° C. In some embodiments, step (iv) comprises centrifuging the third solution at about 15,000 rpm for about 3 minutes at a temperature of about 15° C. The method further includes vortexing and sonicating the third solution in water prior to centrifuging the third solution to obtain cerium (III) carbonate. In some embodiments, the method further includes vortexing the third solution for about 1 minute to about 10 minutes and then sonicating the third solution for about 1 minute to about 10 minutes, where the vortexing and sonicating is performed in water prior to centrifuging the third solution to obtain cerium (III) carbonate. In some embodiments, the method further includes vortexing the third solution for about 5 minutes and then sonicating the third solution for about 5 minutes, where the vortexing and sonicating is performed in water prior to centrifuging the third solution to obtain cerium (III) carbonate.

[0099] The present disclosure provides cerium (III) carbonate produced by the methods described herein. In some embodiments, the cerium (III) carbonate releases at least 28.4 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate. In some embodiments, the cerium (III) carbonate releases at least 28.5 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate releases at least 29.0 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate source material. In some embodiments, the cerium (III) carbonate is a cerium (III) carbonate source material as described in detail herein. In some embodiments, the cerium (III) carbonate is Ce2(CO3)3·4H2O.

[0100] In one embodiment, the present invention relates to a method for producing cerium (III) carbonate that releases at least 28 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate source material, the method comprising: (i) mixing ammonium carbonate with ammonium cerium (III) nitrate tetrahydrate, ammonium cerium (III) nitrate, or a combination thereof; (ii) washing with water; and (iii) centrifuging to recover the cerium (III) carbonate from the suspension. In one embodiment, step (i) comprises mixing ammonium carbonate with ammonium cerium (III) nitrate tetrahydrate. In one embodiment, step (i) comprises mixing ammonium carbonate with ammonium cerium (III) nitrate. In one embodiment, the step of mixing ammonium carbonate with ammonium cerium (III) nitrate tetrahydrate and / or ammonium cerium (III) nitrate is performed at a pH of about 9.0-9.2 or less. In one embodiment, the cerium (III) carbonate releases at least 29.0 wt. % CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium (III) carbonate. In one embodiment, the cerium (III) carbonate is Ce2(CO3)3·4H2O.

[0101] In one embodiment, the present invention relates to a method for producing cerium (III) carbonate that releases at least 28 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate source material, the method comprising: (i) mixing ammonium carbonate with water to form a first solution; (ii) mixing cerium (III) nitrate with water to form a second solution; (iii) mixing the first and second solutions to form a third solution, wherein the mixing time for mixing the first and second solutions is about 1 minute or less; and (iv) centrifuging the third solution to form cerium (III) carbonate. In one embodiment, the mixing time in step (iii) is about 20 seconds or less. In one embodiment, the mixing time in step (iii) is about 15 seconds or less. In one embodiment, the cerium (III) carbonate releases at least 28.5 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium (III) carbonate. In one embodiment, the cerium (III) carbonate releases at least 29.0 wt. % CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium (III) carbonate. In one embodiment, the cerium (III) carbonate is Ce2(CO3)3·4H2O.

[0102] In one embodiment, the present invention relates to cerium(III) carbonate produced by the methods disclosed herein.

[0103] In one embodiment, the present disclosure provides a method for producing cerium (III) carbonate, comprising mixing a) ammonium carbonate and b) ammonium cerium (III) nitrate in the presence of water. The ammonium carbonate and ammonium cerium (III) nitrate can be mixed in any manner known to one of skill in the art. Exemplary mixing methods are described elsewhere in this disclosure. Exemplary mixing times are further described elsewhere in this disclosure. In one embodiment, the ammonium carbonate and ammonium cerium (III) nitrate are mixed at room temperature. In one embodiment, the ammonium carbonate and ammonium cerium (III) nitrate are mixed in the presence of water at a pH of about 9.0-9.2. In one embodiment, the cerium (III) carbonate produced by this method is free of electrostatically attached carbonate. In one embodiment, the cerium (III) carbonate produced by this method releases at least 27.5 wt% CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium (III) carbonate.

[0104] Manufacturing method of the formulation The formulations described in this disclosure can be manufactured by a variety of different processes, such as the processes exemplified in this disclosure. The formulations can be manufactured in a batch process, a continuous process, or a combination thereof.

[0105] In some embodiments, the cerium (III) carbonate source material is added directly to the formulation as a powder or a wet paste. The powder is then blended into the formulation using a variety of different forces.

[0106] Blending of cerium(III) carbonate into the formulation may include the use of at least one of shear force, extensional force, compression force, ultrasonic energy, electromagnetic energy, thermal energy, or a combination comprising at least one of the foregoing forces or forms of energy, wherein the foregoing forces are exerted by a single screw, multiple screws, intermeshing co-rotating or counter-rotating screws, non-intermeshing co-rotating or counter-rotating screws, reciprocating screws, pinned screws, pinned barrels, rolls, rams, helical rotors, or a combination comprising at least one of the foregoing.

[0107] Mixing involving the aforementioned forces can be carried out in equipment such as single or multiple screw extruders, Buss kneaders, Henschel, helicones, Ross mixers, Banbury, roll mills, molding machines such as injection molding machines, vacuum molding machines, blow molding machines, high shear mixers, speed mixers, and the like, or a combination comprising at least one of the aforementioned devices.

[0108] In some embodiments, cerium(III) carbonate is first mixed with a portion of the organic compound susceptible to photodecomposition to form a masterbatch. The masterbatch may be in the form of a paste or pellets. The masterbatch is then added to the remainder of the composition, such as the solvent (e.g., water), the photocatalytically active pigment, and other ingredients, to form the final formulation.

[0109] In some embodiments, the masterbatch is typically produced in a first batch mixer, such as a Banbury, Waring blender, Henschel mixer, Ross mixer, etc. The masterbatch may be blended into the final composition in a second batch mixer. In some embodiments, the first batch mixer may be different from the second batch mixer. In some embodiments, the first batch mixer may be the same as the second batch mixer.

[0110] In some embodiments, the masterbatch is produced in a first batch process (described above) or, alternatively, in a first continuous process. The masterbatch is then made into the final formulation in a second continuous process. The continuous process employs single and / or twin screw extruders.

[0111] In some embodiments, the masterbatch is produced in a continuous process, while the formulation (the mixture of the masterbatch with the remainder of the paint composition) is produced in a batch process.

[0112] In one embodiment, the present invention relates to a method for producing a formulation comprising cerium(III) carbonate and an organic compound susceptible to photolysis, the method comprising the step of mixing a cerium(III) carbonate source material with the organic compound susceptible to photolysis to produce the formulation. In one embodiment, the method further comprises the step of mixing a photocatalytically active pigment with the cerium(III) carbonate source material and the organic compound susceptible to decomposition. In one embodiment, the photocatalytically active pigment comprises titanium dioxide. In one embodiment, the cerium(III) carbonate source material is added in an amount of about 1 wt% to about 20 wt% relative to the amount of the photocatalytically active pigment. In one embodiment, the cerium(III) carbonate source material is added in an amount of about 1 wt% to about 10 wt% relative to the amount of the photocatalytically active pigment. In one embodiment, the cerium(III) carbonate source material is added in an amount of about 1 wt% to about 5 wt% relative to the amount of the photocatalytically active pigment. In one embodiment, the cerium(III) carbonate source material is added in an amount of about 2 wt% relative to the amount of the photocatalytically active pigment. In one embodiment, the formulation produced by the above method comprises cerium(III) carbonate in the same phase as the photocatalytically active pigment. In one embodiment, the formulation produced by the above method comprises cerium(III) carbonate in a separate phase from the photocatalytically active pigment.

[0113] In one embodiment, the cerium (III) carbonate source material releases at least 21.9 wt% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium (III) carbonate source material releases at least 27.5 wt% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium (III) carbonate source material releases at least 28.5 wt% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium (III) carbonate source material releases at least 29.0 wt% CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium (III) carbonate source material. In one embodiment, the cerium (III) carbonate source material used in the method is white in color. In one embodiment, the cerium (III) carbonate source material used in the method is substantially insoluble in water.

[0114] In one embodiment, the cerium(III) carbonate in the formulation produced by the method is Ce2(CO3)3·4H2O. In one embodiment, the cerium(III) carbonate in the formulation produced by the method is (a) substantially free of cerium(IV), (b) substantially free of cerium oxide phases, or (c) substantially free of cerium(IV) and substantially free of cerium oxide phases. In one embodiment, the molar ratio of cerium(III) to cerium(IV) in the formulation is greater than 1.0.

[0115] In one embodiment, the present disclosure provides a method for preparing a composition comprising cerium(III) carbonate and a dye or pigment or a combination thereof. In one embodiment, the method for preparing the composition includes (i) mixing a) ammonium carbonate and b) ammonium cerium(III) nitrate in the presence of water to form cerium(III) carbonate; and (ii) mixing the prepared cerium(III) carbonate with a dye or pigment or a combination thereof. In one embodiment, the ammonium carbonate and ammonium cerium(III) nitrate are mixed in the presence of water at a pH of about 9.0 to 9.2.

[0116] The cerium carbonate produced by this method can have any of the properties described elsewhere in this disclosure. The cerium (III) carbonate can be mixed with any of the dyes and / or pigments described elsewhere in this disclosure. In one embodiment, the prepared cerium (III) carbonate is mixed with titanium dioxide in step (ii). In one embodiment, the prepared cerium (III) carbonate is mixed with a dye selected from the group consisting of iron oxide, carbon black, cadmium sulfide, toluidene red, chrome orange, chrome yellow, chrome green, and combinations thereof in step (ii). In one embodiment, the prepared cerium (III) carbonate is mixed with a dye selected from the group consisting of iron oxide, carbon black, cadmium sulfide, toluidene red, chrome orange, chrome yellow, chrome green, and combinations thereof in step (ii). In one embodiment, the prepared cerium (III) carbonate is mixed with a dye selected from the group consisting of iron oxide, carbon black, cadmium sulfide, toluidene red, chrome orange, chrome yellow, chrome green, and combinations thereof in step (ii). In one embodiment, the prepared cerium (III) carbonate is mixed with a dye selected from Congo red or methylene blue in step (ii). In one embodiment, the wt% of cerium (III) carbonate in the composition is described elsewhere in this disclosure. In one embodiment, the wt% of the pigment in the composition is as described elsewhere in this disclosure. In one embodiment, the wt% of the dye in the composition is as described elsewhere in this disclosure.

[0117] Method of using a formulation containing cerium(III) carbonate and a UV protectant In one embodiment, the present invention relates to a method of using a formulation comprising cerium(III) carbonate and one or more UV protection agents. The cerium(III) carbonate and UV protection agents in the formulation are described elsewhere in this disclosure. In one embodiment, the UV protection agent is a UV filtering agent.

[0118] In one embodiment, the present invention relates to a method for reducing ultraviolet skin exposure in a subject, comprising topically administering an effective amount of a formulation comprising cerium(III) carbonate and one or more UV protection agents. In one embodiment, topically administering an effective amount of a formulation comprising cerium(III) carbonate and one or more UV protection agents comprises topically administering an effective amount of a topical lotion comprising cerium(III) carbonate and one or more UV protection agents. In one embodiment, the UV protection agent is a UV filtering agent.

[0119] In one embodiment, the present invention relates to a method for preventing oxidative damage from UV exposure, comprising topically administering an effective amount of a formulation comprising cerium(III) carbonate and one or more UV protection agents. In one embodiment, topically administering an effective amount of a formulation comprising cerium(III) carbonate and one or more UV protection agents comprises topically administering an effective amount of a topical lotion comprising cerium(III) carbonate and one or more UV protection agents. In one embodiment, the UV protection agent is a UV filtering agent.

[0120] In one embodiment, the present invention relates to a method for preventing sun damage in a subject due to exposure to ultraviolet light, the method comprising topically administering an effective amount of a formulation comprising cerium(III) carbonate and one or more UV protection agents. In one embodiment, the present invention relates to a method for preventing sun damage in a subject due to exposure to ultraviolet light, the method comprising topically administering an effective amount of a formulation comprising cerium(III) carbonate and one or more UV filtering agents. In one embodiment, the step of topically administering an effective amount of a formulation comprising cerium(III) carbonate and one or more UV protection agents comprises topically administering an effective amount of a topical lotion comprising cerium(III) carbonate and one or more UV protection agents. In one embodiment, the step of topically administering an effective amount of a formulation comprising cerium(III) carbonate and one or more UV protection agents comprises topically administering an effective amount of a topical lotion comprising cerium(III) carbonate and one or more UV filtering agents.

[0121] In one embodiment, the present invention relates to methods of using cerium(III) carbonate for UV protection of the skin. Types of cerium(III) carbonate useful in these methods are described elsewhere in this disclosure. The cerium(III) carbonate may be present in a formulation. In one embodiment, the cerium(III) carbonate is administered as a dry powder. In one embodiment, the cerium(III) carbonate is administered as a dry powder formulation. In one embodiment, the cerium(III) carbonate is administered as part of a lotion (e.g., a sunscreen formulation). In one embodiment, the cerium(III) carbonate is administered as part of a liquid formulation. In one embodiment, the cerium(III) carbonate is administered as part of a solid or semi-solid formulation. In one embodiment, the cerium(III) carbonate may be present in a formulation further comprising one or more UV protection agents. Exemplary formulations comprising cerium(III) carbonate and UV protection agents and / or UV filtering agents are described elsewhere in this disclosure. In one embodiment, the cerium(III) carbonate is applied to the skin of a subject in the presence of air. In one embodiment, the UV protection agent is a UV filtering agent.

[0122] In one embodiment, the present invention relates to a method of reducing ultraviolet skin exposure in a subject, the method comprising topically administering an effective amount of cerium(III) carbonate. Types of cerium(III) carbonate useful in these methods are described elsewhere in this disclosure. The cerium(III) carbonate may be present in a formulation. In one embodiment, the cerium(III) carbonate is administered as a dry powder. In one embodiment, the cerium(III) carbonate is administered as a dry powder formulation. In one embodiment, the cerium(III) carbonate is administered as part of a lotion (e.g., a sunscreen formulation). In one embodiment, the cerium(III) carbonate is administered as part of a liquid formulation. In one embodiment, the cerium(III) carbonate is administered as part of a solid or semi-solid formulation. In an embodiment, the cerium(III) carbonate may be present in a formulation further comprising one or more UV protection agents. Exemplary formulations comprising cerium(III) carbonate and UV protection agents and / or UV filtering agents are described elsewhere in this disclosure. In one embodiment, the cerium(III) carbonate is applied to the skin of a subject in the presence of air. In one embodiment, the UV protection agent is a UV filtering agent.

[0123] In one embodiment, the present invention relates to a method for preventing oxidative damage from UV exposure, comprising topically administering an effective amount of cerium(III) carbonate. Types of cerium(III) carbonate useful in these methods are described elsewhere in this disclosure. The cerium(III) carbonate may be present in a formulation. In one embodiment, the cerium(III) carbonate is administered as a dry powder. In one embodiment, the cerium(III) carbonate is administered as a dry powder formulation. In one embodiment, the cerium(III) carbonate is administered as part of a lotion (e.g., a sunscreen formulation). In one embodiment, the cerium(III) carbonate is administered as part of a liquid formulation. In one embodiment, the cerium(III) carbonate is administered as part of a solid or semi-solid formulation. In some embodiments, the cerium(III) carbonate may be present in a formulation further comprising one or more UV protection agents. Exemplary formulations comprising cerium(III) carbonate and UV protection agents and / or UV filtering agents are described elsewhere in this disclosure. In one embodiment, the cerium(III) carbonate is applied to the skin of a subject in the presence of air. In one embodiment, the UV protection agent is a UV filtering agent.

[0124] In one embodiment, the present invention relates to a method for preventing sun damage in a subject due to exposure to ultraviolet radiation, the method comprising topically administering an effective amount of cerium(III) carbonate. Types of cerium(III) carbonate useful in these methods are described elsewhere in this disclosure. The cerium(III) carbonate may be present in a formulation. In one embodiment, the cerium(III) carbonate is administered as a dry powder. In one embodiment, the cerium(III) carbonate is administered as a dry powder formulation. In one embodiment, the cerium(III) carbonate is administered as part of a lotion (e.g., a sunscreen formulation). In one embodiment, the cerium(III) carbonate is administered as part of a liquid formulation. In one embodiment, the cerium(III) carbonate is administered as part of a solid or semi-solid formulation. In some embodiments, the cerium(III) carbonate may be present in a formulation further comprising one or more UV protection agents. In one embodiment, the cerium(III) carbonate is applied to the skin of the subject in the presence of air. Exemplary formulations comprising cerium(III) carbonate and UV protection agents and / or UV filtering agents are described elsewhere in this disclosure. In one embodiment, the UV protection agent is a UV filtering agent.

[0125] In one embodiment, the present invention relates to a method for consuming reactive oxygen species synthesized by exposure of the skin to ultraviolet light, the method comprising placing cerium(III) carbonate on the skin. Types of cerium(III) carbonate useful in these methods are described elsewhere in this disclosure. The cerium(III) carbonate may be present in a formulation. In one embodiment, the cerium(III) carbonate is administered as a dry powder. In one embodiment, the cerium(III) carbonate is administered as a dry powder formulation. In one embodiment, the cerium(III) carbonate is administered as part of a lotion (e.g., a sunscreen formulation). In one embodiment, the cerium(III) carbonate is administered as part of a liquid formulation. In one embodiment, the cerium(III) carbonate is administered as part of a solid or semi-solid formulation. In some embodiments, the cerium(III) carbonate may be present in a formulation further comprising one or more UV protection agents. Exemplary formulations comprising cerium(III) carbonate and UV protection agents and / or UV filtering agents are described elsewhere in this disclosure. In one embodiment, the cerium(III) carbonate is applied to the skin of a subject in the presence of air. In one embodiment, the UV protection agent is a UV filtering agent.

[0126] Without wishing to be bound by theory, it is believed that the cerium(III) carbonate present in the formulation in all of the above methods using a formulation comprising cerium(III) carbonate and one or more UV protection agents and / or UV filtering agents acts as a photoprotectant. Without wishing to be bound by theory, it is believed that the cerium(III) carbonate present in the formulation in all of the above methods using a formulation comprising cerium(III) carbonate and one or more UV protection agents and / or UV filtering agents directly removes ROS by catalytically decomposing ROS. In one embodiment, the UV protection agent is a UV filtering agent.

[0127] Method for inhibiting photodecomposition of organic compounds In one embodiment, the present invention relates to a method for inhibiting photolysis of an organic compound, the method comprising mixing cerium(III) carbonate with an organic compound, thereby inhibiting photolysis of the organic compound. In one embodiment, the organic compound is an organic compound susceptible to photolysis. The organic compound can be any organic compound known to one of skill in the art to be susceptible to photolysis. In one embodiment, the organic compound susceptible to photolysis is an organic dye or pigment as described elsewhere in this disclosure. In one embodiment, the organic compound susceptible to photolysis is methylene blue or congo red. Cerium(III) carbonate is described elsewhere in this disclosure.

[0128] In one embodiment, cerium(III) carbonate can photoprotect organic compounds regardless of their charge and therefore inhibit photodecomposition of organic compounds. In one embodiment, any organic compound that is susceptible to reaction with ROS can be photoprotected by cerium(III) carbonate. EXAMPLES

[0129] The following examples are illustrative and are not intended to limit the spirit or scope of the disclosure or claims.

[0130] Example 1 Synthesis of insoluble Ce(III) compounds by precipitating Ce(III) on P25 photocatalytically active pigments. This example compares the effectiveness of photopassivation of a cerium(III) compound (ammonium cerium(III) nitrate) dissolved in a solvent with that microprecipitated close to the oxide pigment surface.

[0131] Step A. Preparation of an aqueous mixture of cerium(III) ammonium nitrate tetrahydrate and ammonium carbonate. 0.52 grams (g) of solid ammonium carbonate was added to a plastic vial and mixed with 2.65 milliliters (mL) of deionized (DI) water to obtain a clear solution. Separately, 87.7 mg of ammonium cerium (III) nitrate tetrahydrate was added to 3.5 mL of DI water and vortexed for 30 seconds (sec) to obtain a clear solution. Then, the Ce(III) salt-containing aqueous solution (i.e., ammonium cerium (III) nitrate tetrahydrate) was added to the ammonium carbonate solution under vigorous stirring and N2 flow. The pH of the resulting solution was about pH 9.1 ± 0.1. This solution was used directly to prepare a mixture with P25.

[0132] Step B. Pretreatment of P25 with TAMOL™ 1124 In a round bottom flask, 6 g of P25, 68 μL of TAMOL™ 1124, and 10 mL of water were added and stirred at 500 revolutions per minute (rpm) for 1 hour (h). TAMOL™ 1124 (hydrophilic copolymer polyelectrolyte) was obtained from DOW Chemical Company and is a pigment dispersant. TAMOL™ 1124 is a hydrophilic copolymer used in a wide range of latex paint formulations from high gloss enamels to low gloss flats. TAMOL™ 1124 provides stability and compatibility with latex paint additives. TAMOL™ 1124 provides compatibility with pigments for good color acceptance and is low foaming and easy to use. The resulting mixture was centrifuged at 14000 rpm for 5 minutes (min). The centrifuged product was washed with 100 mL of DI water to remove excess TAMOL™ 1124 and recentrifuged at 1400 rpm for 5 min. The washing and centrifugation was repeated one more time and the final product was stored as a wet paste with a solid mass content of 48.1 wt % based on the total mass of the paste.

[0133] Step C. Deposition of Ce(III) onto P25 pigment photocatalyst The Ce(III) precursor solution obtained above was added to a plastic vial containing 2.08 g of the TAMOL™ treated wet paste of P25 obtained above (48.07 wt%). The resulting paste was high shear mixed at 3500 rpm to a slurry and subsequently stirred for 1 h. The mixture was then centrifuged at 14000 rpm for 5 min and the product was washed with 100 mL of DI water by vortex mixing for 5 min followed by recentrifugation. The washing and centrifugation cycle was repeated two more times and the product was stored as a wet paste designated Ce(III)-P25. The Ce(III)-P25 wet paste was dried in a freeze dryer for 16 h prior to its use in photopassivation experiments.

[0134] A comparative study of the photodegradation kinetics of methylene blue organic dye using dissolved ammonium cerium(III) nitrate in aqueous solution in the presence of the same amount of unmodified P25, and using a cerium(III) compound microprecipitated close to the oxide pigment surface of P25 (i.e., Ce(III)-P25). This experiment was performed to demonstrate the inhibition of photodegradation processes of organic molecules by insoluble cerium(III) compounds. To evaluate the inhibition of photodegradation processes of organic molecules (e.g., methylene blue (MB) dye) associated with photogenerated reactive oxygen species (ROS) in the presence of P25, a soluble cerium(III) salt in aqueous solution (i.e., cerium(III) ammonium nitrate tetrahydrate) was also used as a ROS scavenger.

[0135] Two separate aqueous solutions of ammonium cerium(III) nitrate were prepared by dissolving 2.5 mg of ammonium cerium(III) nitrate in 9.9 mL of DI water and 10 milligrams of ammonium cerium(III) nitrate in 9.9 mL of water. The pH of both solutions was adjusted to pH 9.1 using ammonium hydroxide (NH4OH). After stirring each solution for 15 minutes, 0.1 mL of the 10 milligrams was added to each solution. -3 A molar concentration (M) of MB organic dye was added to each cerium(III) ammonium nitrate solution to bring the MB dye concentration in both solutions to 10-5 The temperature was maintained at 25° C. 1 mg of P25 powder was added to each solution. Each solution containing P25, MB organic dye, and cerium(III) ammonium nitrate was separately irradiated with 254 nm ultraviolet (UV) light (150 lumens) in a closed photoreactor at 25° C.

[0136] After equal intervals of UV exposure, aliquots were taken from the reaction mixture and centrifuged to remove the photocatalyst. The amount of remaining MB organic dye in the supernatant was quantified by UV-visible spectrophotometry, and these data points were plotted in the graph of Figure 1 as -lnA versus time plot (A stands for "concentration") to represent the pseudo-first order rate constant for the photodegradation of MB organic dye.

[0137] Separately, photocatalysis experiments were performed using a combination of 1 mg of P25 and 1 mg of insoluble Ce(III)-P25 (which represents a cerium(III) compound precipitated on the surface of an oxide pigment photocatalyst). In this photocatalysis experiment, no soluble cerium(III) salts were present. The efficiency of photopassivation was compared to a system using a water-soluble cerium(III) salt (soluble cerium(III) nitrate) by the rate of photodegradation of MB organic dye. The results are shown in Figure 1A-1C. Figure 1A is a graph of the photodegradation of MB dye under 254 nm light at pH 9.1 using 1 mg of P25 in the presence of 2.5 mg of soluble (dissolved) ammonium cerium(III) nitrate. Figure 1B is a graph of the photodegradation of MB dye under 254 nm light at pH 9.1 using 1 mg of P25 photocatalyst in the presence of 10 mg of ammonium cerium(III) nitrate. FIG. 1C is a graph of the photodegradation of MB dye under 254 nm light at pH 9.1 using 1 mg of P25 in the presence of 1 mg of insoluble Ce(III)-P25.

[0138] The data in Figure 1A show a high rate of photodegradation of MB dye by 1 mg of P25 in the presence of 2.5 mg of soluble cerium(III) ammonium nitrate, with a calculated rate constant of 0.32 min -1In Figure 1B, increasing the amount of soluble cerium(III) ammonium nitrate by a factor of four (to 10 mg) reduced the rate of dye degradation by a factor of about six, with a rate constant of 5.5 × 10 -2 min -1 When Ce(III)-P25 (containing cerium(III) carbonate) was used to inhibit MB organic dye, the amount of MB organic dye photodegraded by a total of about 2 mg of P25 (rather than 1 mg as in the study containing soluble salts above) was 64 times lower than the MB dye photodegradation rate obtained using 2.5 mg of soluble cerium(III) salts above (rate = 5 × 10 -3 min -1 (see Figure 1C). Thus, even with twice the amount of photocatalyst, the use of an insoluble cerium(III) compound results in a significantly slower rate of decomposition of the organic MB dye, especially when compared to a composition containing a soluble cerium salt and a lower amount of photocatalyst.

[0139] Assuming that the theoretically maximum amount of cerium(III) was deposited close to the surface of the P25 photocatalyst during the synthesis of Ce(III)-P25 containing insoluble cerium(III) compounds, 87.7 mg of ammonium cerium(III) nitrate would be provided for 1 g of P25. This means that 1 mg of Ce(III)-P25 used in the photocatalysis experiments above contains only 0.087 mg of ammonium cerium(III) nitrate by mass. This amount of cerium(III) compound is 29 times smaller and 115 times smaller than the amount that would be contained in 2.5 mg and 10 mg of water-soluble ammonium cerium(III) nitrate, respectively. However, the inhibitory effect of the insoluble cerium(III) compound on the photodegradation of MB organic dye is much higher than when the cerium(III) compound is soluble.

[0140] Without being limited by theory, this is believed to be a result of the photocatalytic effect being significantly higher when insoluble cerium(III) compounds are used compared to when soluble cerium(III) compounds are used, or a result of an effect of proximity between the cerium(III) compound and the surface of the oxide pigment photocatalyst. Example 3 investigated the latter effect.

[0141] These results show that there is a significant advantage in terms of photopassivation efficiency when using insoluble cerium(III) compounds. The photopassivation in the above examples works even when there is no contact between the cerium(III) compounds and P25 (i.e., about half of the P25 in the above examples does not consist of cerium(III) compounds in contact with its surface, but rather consists of bare P25 without cerium(III) compounds). It was unexpectedly discovered that cerium(III) compounds that are distant from this bare P25 can efficiently suppress its photoactivity. In other words, the suppression of the photocatalyst photoactivity by cerium(III) compounds even in the absence of contact between the cerium(III) compounds and the photocatalyst is a synergistic effect that has not been observed before.

[0142] While the above examples surprisingly demonstrate the effectiveness of photopassivation of cerium(III) compounds when not in contact with the photocatalyst (not in contact with the photocatalyst but located close to the photocatalyst), it can be further demonstrated that photopassivation by a remote action mechanism also operates in compositions containing other oxide pigments or fillers.

[0143] To demonstrate the effect of other pigments, cerium(III) compounds were precipitated in the presence of SiO2 nanoparticles, in the presence of rutile TiO2 (particle size 300 nm), and in the presence of commercial pigments such as Ti-Pure R706 (particle size 300 nm; which itself exhibits some photocatalytic activity) in a manner similar to that used to precipitate cerium(III) compounds in the presence of P25 (see Example 2). In addition to the precipitation of Ce(III) compounds in the presence of oxides, we also prepared another insoluble phase of Ce(III) compounds that is even more effective at inhibiting the photodecomposition of organic matter in slurries containing photocatalysts (see Example 3).

[0144] These examples, i.e. those containing Ce(III)-modified SiO2, Ce(III)-modified TiO2, or Ce(III)-modified Ti-R706 in the dispersion, as well as a Ce(III) compound in a separate phase, all demonstrate that they inhibit the photodegradation of organic dyes to a significantly greater extent than soluble ammonium cerium(III) nitrate (see below), and surprisingly do so by a remote action mechanism (meaning that no physical contact between the photocatalyst and the cerium(III) compound is observed).

[0145] Insoluble Ce(III) compounds are obtained by precipitating cerium(III) compounds on SiO2 (SiO2 particles with diameters of 20 nm to 60 nm): Synthesis: The precipitation of cerium(III) compounds near SiO2 was carried out in the same manner as in Example 1 above, with some changes: (i) in step A of the synthesis, 0.52 g of ammonium carbonate was dissolved in 5 mL of water (instead of 2.63 mL in Example 1), and 1 g (instead of 87.7 mg) of ammonium cerium(III) nitrate tetrahydrate was dissolved in 18 mL of water; (ii) in step B, 1 g of SiO2 powder (average particle size 20 nm to 60 nm, Skyspring Nanomaterials) was used instead of P25. (iii) in step C above, a mixture of ammonium Ce(III) nitrate and ammonium carbonate (obtained in step A above) having a pH of 9.1±0.1 was introduced into the SiO2 wet paste (obtained in step B above) instead of P25, to finally precipitate cerium(III) carbonate on the SiO2. The final product was dried in a freeze dryer for 16 hours, and the dried product was bright white in color (see FIG. 2A).

[0146] Photostabilization of MB organic dyes using Ce(III)-SiO2: Figure 2B shows the results of a 10 mL 1000-mL experiment using 50 mg of P25 photocatalyst in the presence of 5 mg of Ce(III)-SiO2. -5 Figure 1 shows a pseudo-first order plot of the photodegradation of MB organic dye in M-lnA versus time. The rate constant of decomposition of MB organic dye calculated from this plot is 3.1 x 10 -3 min -1It was found that. Assuming that the maximum possible amount of cerium(III) compound was precipitated close to the SiO2 surface during the synthesis of Ce(III)-SiO2, 1 g of ammonium cerium(III) nitrate would be provided per g of SiO2. This means that 1 mg of Ce(III)-SiO2 used for the photocatalytic degradation of MB organic dyes can contain up to 1 mg of ammonium cerium(III) nitrate. This amount of cerium(III) is 1 / 2.5 and 1 / 10 of the amount present in 2.5 mg and 10 mg of water-soluble ammonium cerium(III) nitrate, respectively, in Example 1 above.

[0147] However, the data in Figure 2B confirm that the photodegradation rate of MB organic dye by Ce(III)-SiO2 is reduced by 103 and 18 times compared to the photodegradation rate obtained in the presence of 2.5 mg and 10 mg of water-soluble ammonium cerium(III) carbonate, respectively, in Example 1. It is also noteworthy that the photodegradation of MB organic dye was achieved by adding only 1 mg of P25, which requires 55 times less photocatalyst than when Ce(III)-SiO2 was used as a passivating agent.

[0148] Based on the data in Figure 2B, it can be seen that the aqueous cerium(III) nitrate is a significantly less effective photopassivating agent compared to the insoluble cerium(III) compound used in Ce(III)-SiO2. Furthermore, the mechanism of action of the latter material as a photopassivant is a remote action mechanism that does not require contact with the P25 surface for the Ce(III)-SiO2 to be effective as a photopassivator.

[0149] Photopassivation of MB organic dyes using Ce(III)-TiO2-commercial grade rutile titania (particle size 300 nm) where Ce(III) was precipitated to form a solid mixture containing rutile and cerium(III) carbonate: Synthesis: The precipitation of cerium(III) compounds near TiO2 was carried out similarly to Example 1, with some modifications: (i) in step A of the synthesis, 0.52 g of ammonium carbonate was dissolved in 5 mL of water (instead of 2.63 mL in Example 1), and 1 g of ammonium cerium(III) nitrate tetrahydrate (instead of 87.7 mg used in Example 1) was dissolved in 18 mL of water; (ii) in step B of the synthesis, 100 g of TiO2 powder (US Research Nanomaterials) was used instead of P25. (pure rutile without photopassivation layer, with an average particle size of 300 nm, obtained from TAMOL™ 1124, Inc.) was added to a round bottom flask containing 1 mL of TAMOL™ 1124 and 100 mL of DI water and stirred at 500 rpm for 1 hour; (iii) in step C, a mixture of ammonium cerium (III) nitrate and ammonium carbonate (obtained in step A) was introduced into a 73 wt % aqueous slurry containing 11.4 g of TiO2 powder (instead of P25 used in example 1) and stirred for 1 hour before centrifugation and washing. The resulting final product was dried in a freeze dryer for 16 hours to give a white dried product with a light off-white tint, as shown in FIG. 3A.

[0150] Figure 3B shows a 10 mL aqueous slurry containing 2 mg of P25 in the presence of 5.7 mg of Ce(III)-TiO2 (i.e., a surface area ratio of P25 to Ce(III)-TiO2 of 1:0.8). -5 3B is a graph of lnA versus time showing a pseudo-first-order plot for the decomposition of MB organic dye in M. The rate constant for MB organic dye photodecomposition calculated from the data in FIG. 3B is 7.9×10 -4 min -1 Elemental analysis by neutron activation analysis revealed that Ce(III)-TiO2 contained 4.35 wt% cerium by mass relative to TiO2, which means that 5.7 mg of Ce(III)-TiO2 used in the photocatalytic reaction of MB dye contained 0.245 mg of cerium, whereas 2.5 mg and 10 mg of aqueous cerium(III) ammonium nitrate contained 0.625 mg and 2.5 mg of cerium, respectively.

[0151] Despite the much higher amount of cerium in the soluble ammonium cerium(III) carbonate than in the insoluble cerium(III) compound used in Ce(III)-TiO2, the rate constant for the photodegradation of MB organic dye was observed to be 400- and 69-fold lower with Ce(III)-TiO2 than with 2.5 and 10 mg of soluble ammonium cerium(III) carbonate.

[0152] Thus, water-soluble ammonium cerium(III) nitrate is a significantly less effective photopassivator than cerium(III) carbonate deposited on rutile TiO2. Even more surprising, since P25 is located on a separate particle from the one closely precipitated by the insoluble Ce(III) compound, the action of the latter material as a photopassivator must be via a remote mechanism.

[0153] Example 2 The significance of a Ce(III):Ce(IV) molar ratio greater than 1 (i.e., exceeding 1) in cerium(III) compounds used for photopassivation Synthesis: The deposition of cerium(III) compounds near Ti-Pure R706 was carried out in the same manner as in Example 1, with some modifications: (i) in the above step A of the synthesis, 0.52 g of ammonium carbonate was dissolved in 5 mL of water (instead of 2.63 mL in Example 1), and 1 g of ammonium cerium(III) nitrate tetrahydrate was dissolved in 18 mL of water; (ii) in step B, 100 g of Ti-Pure R706 powder (having an average particle size of 300 nm, The Chemours, 2002) was used instead of the P25 photocatalyst. (iii) In step C above, a mixture of ammonium cerium(III) nitrate and ammonium carbonate with a pH of 9.1±0.1 (obtained in step A) was introduced into a 73 wt % aqueous slurry containing 11.4 g of R706 (substitute for P25 used in example 1) and the resulting slurry was stirred for 1 hour before centrifugation and washing. Drying in a freeze dryer for 16 hours afforded the final product, Ce(III)-R706 (which represents Ti-Pure R706 modified with cerium(III)), which was a bright white powder as shown in FIG. 4B. FIG. 4A is a photograph showing Ti-Pure R706 before modification with insoluble cerium(III) compounds. It can be seen that there is virtually no difference in color between the modified and unmodified Ti-Pure R706.

[0154] Comparison of the photodegradation of MB organic dyes in aqueous solution by P25 photocatalyst in the presence of Ce(III)-R706 (under 254 nm light irradiation) and unmodified Ti-Pure R706 (under 254 nm light irradiation). Photocatalytic degradation of MB organic dye was carried out in an aqueous slurry of 1 mg of P25 photocatalyst in the presence of 5.7 mg of Ce(III)-R706 or unmodified (i.e., no added cerium(III) compound) Ti-Pure R706. The resulting surface area of ​​P25 was 57 m2 / g, and the surface area of ​​R706 is 10 m 2 / g, the surface area of ​​P25 and either Ce(III)-R706 or Ti-Pure R706 are comparable. The results are shown in Figures 5A and 5B. Figure 5A is a -lnA vs time plot for the degradation of MB organic dye by P25 in the presence of Ce(III)-R706, while Figure 5B is a -lnA vs time plot for the degradation of MB organic dye by P25 in the presence of unmodified R706.

[0155] From the data shown in Figures 5A and 5B, the rate constant for the photodegradation of the MB organic dye is 0.61 min -1 (Figure 5B, when Ti-Pure R706 was added to the slurry) to 8.3 × 10 -4 min -1 (Figure 5A, when Ce(III)-R706 was added to the slurry). These results indicate that unmodified Ti-Pure R706 alone cannot effectively suppress the photocatalytic activity of P25 photocatalyst like Ce(III)-R706 can.

[0156] Photodegradation of MB organic dye in aqueous solution by P25 photocatalyst (under 254 nm light) compared with that using a variant containing a mixed-valence Ce(III) / Ce(IV)-R706 material in which an equimolar mixture of cerium(III) and cerium(IV) was deposited in close proximity to the surface of Ti-Pure R706. To understand the minimum amount of Ce(III)-R706 required to efficiently inhibit the photodegradation of MB organic dyes, a series of photocatalytic reactions were performed in which the amount of Ce(III)-R706 was varied while the amount of P25 in the aqueous dispersion was kept fixed. The results of this experiment are shown in Figure 6A in terms of the rate constant of the photodegradation of MB organic dyes as affected by the ratio of the surface area of ​​Ce(III)-R706 to the surface area of ​​the P25 photocatalyst. Figure 6A shows the relationship between the mass fraction of Ce(III)-R706 relative to P25 and the rate constant of the photodegradation of MB organic dyes at 10 -51 is a plot of the photodegradation rate constant for the decomposition of MB organic dye with M. The data shows that when this molar ratio is 0.2 or greater, the photodegradation of MB organic dye is inhibited very effectively.

[0157] The effect of the cerium valence state on the photopassivation of cerium compounds was also investigated by comparing pure cerium(III) with an equimolar mixture of cerium(III) and cerium(IV) valence states. For this comparison, a new material, Ce(III) / Ce(IV)-R706, was obtained by deposition of cerium on the surface of Ti-Pure R706 from an equimolar mixture of cerium(III) and cerium(IV) salts. Ce(III) / Ce(IV)-R706 was thus synthesized similarly to Ce(III)-R706 (obtained in Example 2), with the following modifications: (i) in step A of the synthesis, 0.52 g of ammonium cerium(III) nitrate tetrahydrate and 0.495 g of ammonium cerium(IV) nitrate (the solution has equimolar amounts of cerium(III) and cerium(IV)) were dissolved in 18 mL of water;

[0158] The photocatalytic effectiveness of Ce(III) / Ce(IV)-R706 was evaluated by varying the relative amounts of Ce(III) / Ce(IV)-R706 and using a 10% ZnO / ZnO mixture containing a constant amount of P25 photocatalyst. -5 The photocatalysis was performed on a 10 mL dispersion of MB organic dye at 100 nm, similar to the Ce(III)-R706 in the above paragraph. The results are shown in Figure 6B. Figure 6B shows the effect of the Ce(III) / Ce(IV-R706) mass fraction on P25 at 10 -5 1 is a plot of the photodegradation rate constant for the decomposition of MB organic dye at M.

[0159] As can be seen, the rate constant for the photodegradation of MB organic dye is significantly larger with Ce(III) / Ce(IV)-R706 compared to Ce(III)-R706 at the same value on the x-axis. Even at the highest investigated mass fraction of 1, the rate constant for the photodegradation of MB organic dye was almost 10 times lower with Ce(III)-R706 in Figure 6A compared to Ce(III) / Ce(IV)-R706 passivator in Figure 6B. Thus, this data clearly shows the advantage of using pure cerium(III) compounds rather than mixed-valence compounds consisting of both cerium(III) and cerium(IV) valence states in materials used to inhibit the photodegradation of organics.

[0160] Photostabilization of organic dyes in solid (dry) compositions consisting of photocatalyst and Ce(III)-R706: The above examples have been concerned with reducing the photodegradation of organic dyes in the wet (liquid) state. In the following examples we show that a similar approach can be used to achieve effective photopassivation of photocatalysts in the dry (solid) film state.

[0161] To test the effectiveness of this technique in dry (solid) compositions, a concentration of 3 × 10 -5 Congo red (CR) organic dye at M was incorporated into a water-based acrylic paint formulation dispersion along with P25 photocatalyst (10 wt % with respect to the Ti-Pure R706 pigment mass used in the dispersion).

[0162] A 16% Ce(III)-R706 pigment volume concentration composition with CR organic dye was prepared (pigment volume concentration is defined as the volume percentage of solid particles in the system after forming the composition (e.g., excluding water)). This was done by first preparing a 75 wt% aqueous slurry of Ce(III)-R706 pigment by high shear mixing in the presence of 0.3 wt% TAMOL™ 1124, based on the weight of the pigment. 4.64 g of this slurry was incorporated into 12.78 g of acrylic BP 8164 polymer (obtained from Dow Chemical Company) and mixed with 1.966 mL of 3.5×10 -4M of the CR aqueous solution and 10 wt% (with respect to the pigment mass) of P25 photocatalyst were added. The resulting dispersion was mixed under high shear conditions in a high-speed mixer.

[0163] Then, 0.6 g of 2020E thickener (a non-ionic urethane-based rheology modifier) ​​was added into the slurry, and the resulting dispersion was mixed under high shear conditions in a high-speed mixer to obtain the dispersion of the final formulation. Solid (dry) films were prepared using a 3 mil (1 mil = 0.001 inch) bar applicator on polyacrylic substrates and allowed to dry for 48 hours before conducting photocatalysis experiments. During photocatalysis, all coatings were exposed to sunlight (similar conditions) for 6 hours of exposure time. Prior to sunlight exposure, 100 mg of the coating was scraped off with a sharp blade and extracted with 1.5 mL of absolute ethanol for UV-Visible spectroscopy as a reference for the CR organic dye concentration in the film before photocatalysis. Similarly, another 100 mg portion of the coating was scraped off and extracted after 6 hours of sunlight exposure, and the percentage of dye degradation was calculated by UV-Visible spectroscopy. As a control experiment, a formulation dispersion lacking P25 (the control formulation dispersion was synthesized as above except that it lacked P25) was used, and negligible photodegradation of the CR organic dye was observed when the control sample was exposed to sunlight for 6 hours.

[0164] For a dispersion formulation consisting of Ce(III)-R706 and P25 (90%:10% w / w), Figure 7A shows 52% degradation of CR organic dye in a dried film after exposing the film to 6 hours of sunlight. Figure 7A is a plot of absorbance versus wavelength obtained from a UV-visible spectrum of CR dye degradation before and after 6 hours of sunlight exposure in a coating made with 10% photocatalyst P25 and 90% Ce(III)-R706.

[0165] FIG. 7B is a plot of absorbance versus wavelength obtained from the UV-visible spectra of the degradation of CR dye before and after 6 hours of sunlight exposure in a coating made with 10% photocatalyst P25 and 90% unmodified Ti-pure-R706. From FIG. 7B, it can be seen that after the same sunlight exposure, the amount of CR organic dye decomposition was 85% when using a comparative dispersion formulation consisting of unmodified Ti-Pure R706 and P25 (90%:10% w / w). These results indicate a higher inhibition efficiency of the photodegradation of organic dye in the dried coating when using Ce(III)-R706 compared to unmodified R706 in the presence of P25.

[0166] The above experiments demonstrate that Ce(III)-R706 inhibits the photodegradation of organic matter by a remote action mechanism in the solid state. Similar results can be obtained by preparing an equivalent of Ce(III)-R706 using another pigment, such as the rutile TiO2 used in Example 1 (see Figure 3), or another low grade TiO2, a class of pigment material often used in coating compositions.

[0167] Example 3 This example was carried out to demonstrate the photostabilization of organic dyes using alternate phase cerium(III) carbonate.

[0168] Synthesis and characterization In a plastic vial, 1.04 g of solid ammonium carbonate was added and mixed with 5 mL of deionized water to obtain a clear solution. Separately, 2 g of ammonium cerium (III) nitrate tetrahydrate was added to 20 mL of DI water and vortexed for 30 seconds to obtain a clear solution. The aqueous solution containing cerium (III) salt was then added to the aqueous ammonium carbonate solution under vigorous stirring to obtain a mixture with a pH of 9.1 ± 0.1. To ensure a white Ce(III) carbonate product, it is necessary to ensure a sufficiently short mixing time when adding the aqueous Ce(III) salt-containing solution to the ammonium carbonate solution. This mixing time can be less than 4 minutes, less than 1 minute, less than 20 seconds, or less than 15 seconds. The mixture was then stirred for 1 hour and then centrifuged at 15000 rpm for 3 minutes at 15°C. The resulting white product was washed with 100 mL of water by vortexing the aqueous slurry for 5 minutes followed by sonication for 5 minutes before collecting the solids by centrifugation. This washing step was repeated two more times to remove any loosely held ammonia species prior to obtaining a wet paste (after centrifugation) with a solids content of 24.5 wt %. Upon drying a small portion of this wet paste, the resulting powder retained its bright white color, as shown in FIG.

[0169] The empirical formula of the white cerium(III) compound shown in Figure 8 above has been proposed based on thermogravimetric analysis, an approach previously used by Liu et al. (J. Cryst. Growth, 1999, 206, 88-92) and Zhai et al. (Mater. Lett., 2007, 61, 1863-1866). Figure 9 shows the TGA pattern of the white cerium(III) compound. The pattern shows an initial weight loss of about 11.9%, corresponding to the loss of water, followed by a weight loss of 25.7%, corresponding to the loss of CO2.

[0170] At 900 °C, at the end of the TGA experiment, 62.4% of the original mass was retained, which corresponds to the presence of ceria (CeO2). Thus, the TGA data in Figure 9 show that the composition of the Ce dried precursor after synthesis is Ce2(CO3)3·4H2O. Figure 9 shows a graph of weight loss versus temperature run in dry air with a temperature ramp rate of 5 °C / min for cerium(III) carbonate synthesized as described above and dried at 80 °C for 16 hours (h) prior to thermogravimetric analysis.

[0171] Powder X-ray diffraction (PXRD) analysis of the cerium(III) compounds showed sharp lines consistent with a highly crystalline compound. Transmission electron microscopy indicates that the above synthesis results in particle sizes ranging from 5 μm to 10 μm in cross section, although one skilled in the art will recognize that tailoring the synthesis to result in smaller particles, such as those on the length scale of 100 nm or less in cross section, would be more preferable for photopassivation applications, which are generally more effective at high surface-to-volume ratios.

[0172] Photostabilization of MB organic dyes in solution phase using alternative cerium(III) carbonate: In all of the above examples, the insoluble cerium(III) compounds functioning as photopassivators were in the form of precipitates close to the surfaces of inorganic oxide pigment particles (e.g., rutile TiO, Ti-Pure R706, silica, etc.).

[0173] In Example 3, the possibility of incorporating a cerium(III) compound as a separate phase as an effective photopassivator was investigated.

[0174] This investigation was prompted by the remote action mechanism observed in many of the above examples where efficient quenching of the photocatalyst was achieved even when the cerium(III) compound was not in contact with the photocatalytic surface. For example, examination of the data in Figure 6A shows that the addition of Ce(III)-R706, which has a surface area equivalent to that of P25, reduced the rate constant for the photodegradation of the MB organic dye (by 7.2 × 10 -4 min-1 It was found that the amount of Ce(III)-R706 was 4.4 wt% Ce relative to the mass of R706. This means that the amount of Ce(III)-R706 (11.4 mg used for the photocatalysis of MB organic dye) contains 0.5 mg Ce in Ce(III)-R706. Therefore, an attempt was made to solve the following questions related to this example: To synthesize Ce(III)-R706, it is possible to add 0.5 mg Ce in the cerium(III) carbonate phase without depositing it close to the surface of Ti-Pure R-706, and achieve the same photopassivation by a remote action mechanism.

[0175] Contains 10 mg of P25 and 11.4 mg of Ti-Pure R706 -5 In a MB organic dye aqueous slurry at 100 M, 1.0 mg of Ce2(CO3)3·4H2O particles (corresponding to 0.5 mg of Ce) were incorporated as its own phase. Figure 10 shows the 10 mg P25 in the presence of 2 mg P25, 11.4 mg unmodified Ti-pure R706 and an additional 1 mg Ce2(CO3)3·4H2O. -5 1 is a plot of -lnA vs time for the degradation of MB organic dye (under 254 nm light) of M.

[0176] The rate constant calculated from the data in Figure 10 is 5.5 × 10 -4 min -1 which is 1.5 times lower than the rate constant achieved with the same amount of cerium using Ce(III)-R706 in Figure 6A of Example 2. Based on these results, it was inferred that the incorporation of exogenously prepared insoluble Ce2(CO3)3·4H2O particles is preferable to the precipitation in close proximity to an existing support surface of another phase, e.g., Ti-Pure R706, to suppress the photodegradation of organic molecules.

[0177] Photostabilization of CR organic dyes in solid (dry) films containing R706 and other phases of cerium(III) carbonate: To investigate the photopassivation effect of different cerium(III) compounds in dry (solid) coatings, insoluble cerium(III) carbonate particles and 3×10 -5 A concentration of M of CR organic dye was incorporated into a water-based acrylic paint formulation dispersion and the rate of photodegradation of the dye was evaluated in comparison to the same dispersion in the absence of cerium(III) carbonate particles using either Ti-Pure-R706 as the pigment or the same rutile TiO2 used in Example 1.

[0178] The composition of this dispersion and the procedure for synthesis of the dried coating are described in the following paragraphs. The dispersion consisted of a water-based acrylic paint formulated with unmodified Ti-Pure R706 or rutile TiO2 as the pigment at a pigment volume concentration of 16%. It was first prepared by dissolving 1.966 mL of 3.5 x 10 -4 This was achieved by adding the desired amount of cerium(III) carbonate, corresponding to 2 wt% or 5 wt% by weight of pigment, to an aqueous solution containing M CR aqueous dye solution and 12.78 g of acrylic polymer BP 8164 (a product of Dow Chemical). Separately, 75 wt% aqueous slurries of either Ti-Pure-R706 or rutile TiO2 were prepared by high shear mixing in the presence of 0.3 wt% TAMOL™ 1124 by weight of pigment. 4.64 g of this latter slurry (actual amount of pigment was 3.5 g) was incorporated into the above acrylic polymer-containing slurry and the resulting dispersion was mixed under high shear conditions in a high speed mixer.

[0179] Finally, 0.6 g of 2020E thickener was added to the slurry and the resulting dispersion was mixed under high shear conditions in a speed mixer to obtain the composition. Solid (dry) film coatings were prepared on polyacrylic substrates using a 3 mil bar applicator and allowed to dry for 48 hours before conducting photocatalysis experiments. During photocatalysis, all coatings were exposed to sunlight for 6 hours under similar conditions. Prior to sunlight exposure, 100 mg of the coating was scraped off with a sharp blade and extracted with 1.5 mL of absolute ethanol for UV-Visible spectroscopy as a reference for the CR organic dye concentration in the film before photocatalysis. Similarly, a 100 mg portion of the coating was scraped off after 6 hours of sunlight exposure and the percentage of dye degradation was calculated by UV-Visible spectroscopy compared to the sample before photocatalysis.

[0180] Figures 11A-11C show the extent of degradation of CR organic dye in dried coatings made with unmodified Ti-Pure-R706 after 6 hours of sunlight exposure with varying amounts of separately prepared cerium carbonate. It can be clearly seen from the UV-visible spectra that the extent of photodegradation of CR organic dye decreases with increasing mass % of cerium(III) carbonate relative to Ti-Pure R706 in the coating. In the absence of cerium(III) carbonate, Figure 11A shows 52% photodegradation of CR organic dye with R706 as photocatalyst. Figure 11B shows that the percentage of photodegradation of CR organic dye decreases to 29% when 2 wt% of cerium(III) carbonate is present relative to the mass of Ti-Pure R706 pigment (i.e., 70 mg of Ce2(CO3)3·4H2O for 3.5 g of pigment). Figure 11C shows that the percentage of photodegradation of CR organic dye by Ti-Pure R706 can be further reduced to 12% in the presence of 5% by weight of cerium(III) carbonate relative to the weight of Ti-Pure-R706 (i.e., 175 mg of Ce2(CO3)3·4H2O for 3.5 g of pigment). This data clearly indicates that in the dry film containing only Ti-Pure R-706 as photocatalyst, a separate phase of insoluble cerium(III) compound has photocatalytic function.

[0181] The photopassivation ability of the same insoluble cerium (III) carbonate as another phase was investigated with rutile TiO2 used in Example 1 above (as in the paragraph above) instead of Ti-Pure R-706 as the pigment. Figure 12A shows that in a coating made without a cerium (III) compound, photocatalysis by rutile TiO2 caused 58% photodegradation of the CR organic dye after 6 hours of exposure of the dried film to sunlight (the control in Example 2 consisting of only the polymer and CR organic dye demonstrated no significant photodegradation of the dye in the absence of pigment). The data in Figure 12B show that the extent of dye degradation was reduced to 20% when the coating was made with 2 wt% cerium (III) carbonate relative to the mass of the rutile TiO2 pigment photocatalyst. Surprisingly, the data in Figure 12C show that a coating made with 5 wt% cerium (III) carbonate along with rutile TiO2 showed no detectable photodegradation of the CR dye after 6 hours of sunlight exposure. This last data set shows that inexpensive grades of commercially available TiO2 can be successfully photopassivated by our action-at-a-distance mechanism, using insoluble particles of cerium(III) carbonate as a separate cerium(III) compound phase.

[0182] Example 4 So far, in all the above examples, the Ce-based materials discussed for photopassivation of organic compounds were synthesized according to our synthesis protocol (i.e., synthesis of cerium carbonate shown in Example 3). Here, we evaluated the efficiency of photopassivation of commercially available cerium(III) carbonate hydrate obtained from different chemical suppliers including Sigma Aldrich (325503-50G 99.9% trace metals standard); ACROS organics (AC379400500); Alfa Aesar (15295-22).

[0183] Three separate sets of photocatalytic reactions were carried out using the same conditions and procedures as described in Example 3 (i.e., 10 mL of 10 -5M aqueous methylene blue (MB) solutions were treated with 2 mg of P25 photocatalyst, 11.4 mg of R706, and 1 mg of Ce2(CO3)3·xH2O obtained from different commercial sources (i.e., Alfa Aesar, Sigma Aldrich, and ACROS Organics) in the same photoreactor setup. Surprisingly, Ce2(CO3)3·xH2O obtained from Sigma-Aldrich and ACROS Organics did not show photopassivation of the MB dye, and the MB dye was degraded to about 100% in aqueous solution within 30 seconds under exposure to 254 nm light in the photoreactor. However, Ce2(CO3)3·xH2O obtained from Alfa Aesar showed efficient photopassivation of the MB dye in solution using the procedure described above. Figure 13A shows the kinetics of photodegradation of the MB organic dye obtained from this experiment. The rate constant calculated from the data in Figure 13A is 1×10 -3 min -1 which is still about 2 times faster than the MB degradation achieved with the same amount of Ce2(CO3)3·xH2O synthesized according to Example 3 (see FIG. 10). Ce2(CO3)3·xH2O from Sigma-Aldrich and ACROS organics did not show photopassivation of the MB dye using the procedure described above, but when the amount of Ce2(CO3)3·xH2O was increased from 1 mg to 5 mg, a corresponding amount of photopassivation of the MD dye was observed in both cases (e.g., for the Ce2(CO3)3·xH2O samples from Sigma-Aldrich and ACROS). Figures 13B and 13C show the kinetics for the photodegradation of the MB organic dye obtained from these experiments, with the rate constants calculated from the data in Figures 13B and 13C being 4.7×10 -3 min -1 and 4 x 10 -3 min -1 These data show 8.5-fold and 7.5-fold higher MB degradation under 254 nm light exposure compared to that achieved with the same amount of Ce2(CO3)3·xH2O synthesized according to Example 3 (see FIG. 10).

[0184] ATR-FTIR was performed to investigate the difference in the nature of the carbonate in the various Ce2(CO3)3·xH2O materials. Notable differences in the ATR-FTIR spectra of Ce2(CO3)3·xH2O from Sigma-Aldrich and ACROS organics show that both materials have a peak at 1410 cm corresponding to a weakly electrostatically attached carbonate. -1 The Ce2(CO3)3·xH2O obtained from Alfa Aesar also had a strong peak at 1410 cm, which was similar to the FTIR of free carbonate ion dissolved in water (Geochimica et Cosmochimica Acta, 2005, 69, 1527-1542). -1 Although it showed a band at 1410 cm, it was very weak in intensity compared to the other bands mentioned above (e.g., the unidentate carbonate bands). -1 The band at 1410 cm was completely absent in Ce2(CO3)3·xH2O synthesized according to Example 3. We have found that the band at 1410 cm is an indication of the presence of electrostatically attached carbonate in Ce2(CO3)3·xH2O. -1 (electrostatically attached carbonate) peak intensity and 1468 cm -1 The ratio of the peaks of Ce2(CO3)3·xH2O (monodentate carbonate) was used and the values ​​are presented in Table 1 based on the spectrum shown in Figure 14. From this data, it can be seen that for photopassivation of organics on a 1 mg scale in the presence of 2 mg of P25, Ce2(CO3)3·xH2O with a peak intensity ratio of 0.93 or less is preferred. However, a peak ratio of zero is most preferred (i.e., 1410 cm -1 Ce2(CO3)3·xH2O has a band at 1410 cm in the infrared. -1 With weakly electrostatically bound carbonate as evidenced by the significant band intensity of .alpha., the cerium carbonate has poor photopassivation ability.

[0185] [Table 1]

[0186] To further investigate the difference in the photopassivation ability of commercial Ce2(CO3)3·xH2O and Ce2(CO3)3·4H2O synthesized according to Example 3, CHN elemental analysis was performed. Ce2(CO3)3·xH2O obtained from Sigma-Aldrich and ACROS Organics contained 5.71% C and 0.93% H, and 5.74% C and 0.88% H, respectively, while Ce2(CO3)3·xH2O obtained from Alfa Aesar contained 6.5% C and 1.45% H. Ce2(CO3)3·xH2O synthesized in Example 3 contained 6.7% C and 1.76% H. Based on this data, cerium carbonate with both high C and H contents is preferred. Cerium carbonate with 5.7% or less by weight C and 0.9% or less by weight H is less preferred. Alternatively, the cerium carbonate more preferably has a C mass percentage of 6.5% or more and a H mass percentage of 1.5% or more.

[0187] A further means for characterizing and differentiating batches of cerium carbonate according to the invention is thermogravimetric analysis, which relies on the thermal decomposition of cerium carbonate to synthesize cerium oxide and CO2, and occurs in the temperature range of 200°C to 575°C (see J. Cryst. Growth 1999, 206, 88-92 and Mater. Lett. 2007, 61, 1863-1866). The data in Figure 9 and Table 2 summarize the mass loss over the temperature range 200°C to 575°C, normalized to the dehydration mass at 200°C, during thermogravimetric analysis of various cerium carbonate batches in dry air with a heating ramp rate of 5°C / min. Cerium(III) carbonate synthesized according to Example 3 has the highest mass loss corresponding to released CO2 normalized to the dehydrated mass at 200°C of 29.0% (mass difference between 200°C and 575°C divided by the dry mass at 200°C), while batches of cerium(III) carbonate received from Sigma Aldrich and Acros Organics have lower mass losses of 22.7% and 21.9%, respectively.

[0188] [Table 2]

[0189] Based on these data in Figure 9 and Table 2, it was concluded that the most preferred cerium carbonate has a mass loss corresponding to the CO2 released during thermogravimetric analysis of at least 29.0% when normalized to the dry mass of the material. A more preferred batch of cerium carbonate of the present invention has a mass loss corresponding to the CO2 released during thermogravimetric analysis of at least 27.6% when normalized to the dry mass of the material. A preferred batch of cerium carbonate of the present invention has a mass loss corresponding to the CO2 released during thermogravimetric analysis of at least 21.9% when normalized to the dry mass of the material.

[0190] Based on the above data, all the commercially available Ce2(CO3)3·xH2O are capable of photosenable passivation of organic molecules by a long-distance action mechanism, but they were not as effective as our Ce2(CO3)3·4H2O synthesized according to Example 3 due to the presence of small amounts of carbonate or the presence of electrostatically attached carbonate. Therefore, a larger amount of commercially available Ce2(CO3)3·xH2O is needed to capture the ROS generated by the photocatalysis.

[0191] Example 5 Photocatalysis enhances the photodegradation of organics, which is believed to be mediated by the generation of reactive oxygen species (ROS), but organic molecules are themselves light absorbing due to the presence of light absorbing chemical substituents. This light absorption itself generates radicals in water, ultimately leading to the photodegradation / degradation of organics, even in the absence of a photocatalyst itself. Here, we investigated whether the intrinsic photodegradation / degradation of methylene blue (MB) dye under exposure to 254 nm light could be suppressed by using cerium(III) carbonate in the absence of an added photocatalyst.

[0192] Two separate sets of photoreactions were performed: (1)10 -5 A 10 mL aqueous solution of MB dye in M ​​was exposed to 254 nm light for up to 60 min under a photoreactor setup. (2) 1 mg of Ce2(CO3)3·4H2O synthesized according to the procedure described in Example 3 was added to 10 -5 The data shown in Figures 15A-15B were obtained from a 10 mL aqueous solution of MB dye containing 1 mg of Ce(CO) 4H0. -5 M methylene blue in water is 10 -5 The results demonstrate that the MB dye photodecomposition rate was reduced by approximately 40-fold compared to a control aqueous solution of MB dye at 1 M.

[0193] Example 6 Synthesis of cerium(III) carbonate by solid-state mechanochemical method and its application in photostabilization of organic dyes Synthesis and characterization of cerium(III) carbonate: 1.04 g of solid ammonium carbonate and 2 g of ammonium cerium(III) nitrate tetrahydrate were added to a mortar and ground with a pestle for 5 minutes. The resulting white powder was washed with water (including vortexing for 5 minutes and sonication for 5 minutes) and the solid product was collected via centrifugation at 20,000 rpm for 3 minutes. The solid product was washed three more times to ensure removal of unreacted or loosely held salt species prior to obtaining a wet paste after centrifugation with a solid content of 24.5% by weight. A small portion of this wet paste was dried to obtain a white powder.

[0194] Powder XRD of the mechanochemically synthesized Ce(III) carbonate showed a pattern consistent with crystalline material with the known crystal structure of Ce2(CO3)3·6H2O. As in Example 4, ATR-FTIR was performed to investigate the carbonate nature of Ce2(CO3)3·6H2O. The ATR-FTIR spectrum showed a peak at 1410 cm in Figure 14, similar to the wet-chemically synthesized Ce2(CO3)3·4H2O in Example 3. -1Thermogravimetric analysis in dry air at a heating ramp rate of 5 °C / min showed that 28.4 wt% CO2 was released (mass difference between 200 °C and 575 °C divided by dry mass at 200 °C), and the data are shown in Figure 9.

[0195] The photocatalytic reaction was carried out under the same conditions and procedures as described in Example 3 (i.e., 10 mL of methylene blue (MB) was added to the 10 -5 (The M aqueous solution was treated with 2 mg of P25 photocatalyst, 11.4 mg of R706, and 1 mg of Ce2(CO3)3·6H2O in the same photoreactor setup. Figure 16 shows the kinetics of the photodegradation of MB organic dye obtained from this experiment. The rate constant calculated from the data in Figure 16 is 6 × 10 -4 min -1 which is the same as the rate constant obtained for Ce2(CO3)3 4H2O in Example 3 (i.e., 5.5 × 10 -4 min -1 ) is very similar to

[0196] Example 7 Topical sunscreen lotions based on ultraviolet filtering agents have been developed to limit human exposure to harmful solar radiation, and act to absorb ultraviolet radiation, including UVA in the wavelength range of 315 nm to 400 nm, UVB in the wavelength range of 280 nm to 315 nm, and blue visible light in the wavelength range of 400 nm to 495 nm. However, there is a high unmet need to remove reactive oxygen species (ROS), which are generated when topically applied sunscreen lotions are exposed to sunlight, especially UV rays, as these can oxidize organic molecules in contact with topical sunscreen lotions. These organic molecules include, but are not limited to, antioxidants, organic UV protection agents, organic UV filtering agents, organic components of sunscreen topical lotions (either inactive or active), and skin cells, which are oxidized in the presence of photogenerated ROS. In the latter case, this may involve oxidation of the proteins, lipids, RNA, and DNA of skin cells, which alters their structure and interferes with their biological functions (see Int. J. Mol. Sci. 2013, 14, 12222-12248). This microscopic damage to skin cells, as defined herein, includes the microscopic processes that occur during sunburn.

[0197] Other mammalian cells in the human body may also be damaged, especially those residing in the epidermis and dermis, which are composed of epithelial, mesenchymal, glandular and neurovascular components. High concentrations of ROS have been implicated in human diseases such as melanoma (see Nature 2012, 491, 449-454), tumorigenesis (see Archives of Biochemistry and Biophysics 2014, 563, 51-55 and Journal of Leukocyte Biology 2001, 69, 719-726) and premature aging (see Oxidative Medicine and Cellular Longevity, 2014, Article ID 860479, p. 6). The rate of appearance of ROS in topical sunscreen lotions exposed to sunlight, particularly UV radiation, may be enhanced by the known photocatalytic properties of many UV absorbers (see, e.g., ZnO and TiO2-J. Coat. Technol. Res. 2015, 12, 617-632 and Applied Surface Science 2009, 255, 9006-9009). Attempts have been made to reduce the concentration of ROS in topical sunscreen lotions by adding organic antioxidant compounds to the lotion, since these react with and quench ROS in a stoichiometric reaction that consumes the antioxidant. Examples of antioxidants added to sunscreen lotions include vitamin E (see Nutrition and Cancer 1991, 16, 219-225), green tea extract polyphenols (see Journal of Leukocyte Biology 2001, 69, 719-726), etc. However, these antioxidants, like all organic molecules including organic-based UV protectants (of which vitamin E and green tea polyphenols are examples - see Drug Metabolism Reviews 2000, 32, 413-420), are degraded in the presence of photogenerated ROS (see J. Coat. Technol. Res. 2015, 12, 617-632).

[0198] There is an unmet need for protecting and preserving photodegradable organic molecules that come into contact with sunscreen topical lotions. Provided in the present disclosure are, for example, general compositions and methods for meeting other needs in the art that are not dependent on the charge or composition of the organic molecules or on the specific ingredients in the sunscreen topical lotion.

[0199] In some embodiments, provided herein are sunscreen formulations in which organic molecules are catalytically protected (e.g., in a manner that does not consume photoprotectants). In some embodiments of the formulations and methods provided herein, catalytic (as opposed to stoichiometric) photoprotection of organic molecules is achieved.

[0200] In some embodiments, photoprotection is provided by cerium carbonate hexahydrate Ce2(CO3)3·6H2O added to topical sunscreen formulations containing UV filters. The UV filters may be inorganic, such as metal oxide compositions as described herein (for other metal oxides, ZnO, TiO2, see J. Coat. Technol. Res. 2015, 12, 617-632). In other embodiments, the UV filters may be inorganic. The UV filters may be organic. In some embodiments, the organic UV filter is selected from the group consisting of avobenzone, methyl anthranilate, ecamsule, octyl methoxycinnamate, homosalate, oxybenzone, sulisobenzone, PABA, padimate O, cinoxate, octyl salicylate, trolamine salicylate, octylcrylene, ensulizole, octyl triazone, enzacamene, amiloxate, dioxybenzone, megizolyl XL, tinosorb S, tinosorb M, neoheliopan AP, uvinal Aplus, UVAsorb The active ingredient may be avobenzone, methyl anthranilate, ecamsule, octyl methoxycinnamate, homosalate, oxybenzone, sulisobenzone, PABA, padimate O, cinoxate, octyl salicylate, trolamine salicylate, octylcrylene, ensulizole, octyl triazone, enzacamene, amiloxate, dioxybenzone, megizolyl XL, tinosorb S, tinosorb M, NeoHeliopan AP, Uvinal Aplus, UVAsorb HEB, and combinations thereof. The following examples specifically demonstrate the efficient catalytic ROS scavenging by cerium carbonate, a terrestrially abundant and non-toxic substance, and its photoprotection of a base set of paired charge-containing organic molecular dyes, methylene blue (MB) and Congo red (CR), in various topical sunscreen formulations.

[0201] Example 7.1: Preparation of sunscreen films using methylene blue dye and ZnO-based sunscreen and quantification of dye photodegradation: A commercially available ZnO-based sunscreen (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50, consisting of 21.6% ZnO solids as the only listed active ingredient) was mixed with methylene blue (MB) organic dye as follows: In a plastic cup (10 g capacity; obtained from Flacktek Inc. USA), sunscreen (3 g; Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) and 10 g of ZnO were mixed. -3Aqueous solutions of MB dye (0.6 mL) in water were mixed with a spatula for 3 min. Immediately afterwards, they were subjected to high shear in a Flactek high-speed mixer at 3500 rpm for 3 min. This resulted in a homogenous wet paste with no grains observed, which was employed for drawdown on paper substrates (Whatman filter paper 40; diameter 150 mm) using a 3-mil bar applicator (BYK Additives and Instruments). These wet drawdown coupons were treated with UV light in a photoreactor for various times without drying and then directly extracted. An ethanol solvent was used for extraction to remove the MB dye, allowing quantification before and after UV light exposure, and the extent of MB dye degradation was determined by subtraction. Specifically, two small pieces (100 mg each) were cut from the wet drawdown coupons with scissors / sharp blade to avoid contaminating the applied sunscreen film, and then exposed to UV light in a photoreactor. The photoreactor was equipped with 14 UV lamps with a wavelength of 254 nm and an output of 145–155 lux. The relative humidity during UV exposure was controlled at 100% by placing a Petri dish (volume 200 mL) filled with water in the photoreactor chamber for at least 16 hours before the start of the photocatalytic reaction experiment. After UV exposure, each sunscreen-containing strip was extracted in 2 mL of ethanol by vortex mixing the ethanol and strip for 5 minutes, and then sonicating the strip in ethanol for 10 minutes. The mixture was then centrifuged to separate the solids (all solids were white in color at this point) from the alcohol mixture containing the extracted MB dye. The resulting clear ethanol solution of MB dye was used to measure the MB dye concentration by UV-visible spectroscopy using the absorbance maximum at 654 nm. A control experiment was also performed to quantify the amount of MB dye from a sunscreen film that was not exposed to UV light (at t = 0 time point). In this regard, three strips (100 mg each) were cut from separate wet drawdown coupons and extracted in three different vials with 2 mL of EtOH in each vial. The extent of dye photodegradation was determined by calculating the percentage decrease in the absorbance intensity of the dye at the wavelength of maximum absorption.All experiments were repeated multiple times to measure an indication of the uncertainty associated with each measurement. Using the procedure described above, the extent of MB dye degradation in sunscreens without photoprotectants was measured, and these data are summarized in Figure 17 and Table 3. After 4 hours of UV irradiation, 49±3% of the MB dye in the ZnO-based sunscreen was photodegraded in the absence of added UV protectants.

[0202] [Table 3]

[0203] Example 7.2: Fabrication of ZnO-based sunscreen films incorporating methylene blue dye and UV protection agents and quantification of the degree of dye photodegradation Following the procedure of Example 7.1, similar ZnO-based sunscreen-containing mixtures were formulated with various UV protectants. The amount of photoprotectant incorporated ranged from 0.5 wt% to 1.5 wt% based on the weight of the sunscreen (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50), and the photoprotectants added in this manner included: (a) Ce2(CO3)3·6H2O, and (b) a commercial UV filter ZnO (NANOBYK-3840; composed of 46% ZnO solids as determined by thermogravimetry). In the case of ZnO (NANOBYK-3840), the commercial aqueous dispersion was added directly to the final slurry of sunscreen and MB dye and high shear mixed at 3000 rpm for 3 minutes using the same equipment as in Example 7.1. In the case of Ce2(CO3)3·6H2O, the required amount of Ce2(CO3)3·6H2O wet paste (40 wt% solids) was first added to 0.6 mL of MB dye solution in water, and the mixture was subjected to high shear mixing for 3 minutes. Then, 3 g of sunscreen was added to the mixture, homogenized with a spatula, and then high shear mixed for 3 minutes to obtain a homogenous light blue slurry. Finally, films were prepared in a similar manner as described above for the case without UV protection agent. The extent of dye degradation was measured in a similar manner as described in Example 7.1, and the results are shown in Figures 18A-18B for photoprotector Ce2(CO3)3·6H2O and Figures 19A-19B for photoprotector ZnO (NANOBYK-3840). These data are also summarized in Table 3.

[0204] According to the data in FIG. 18A, when 0.5 wt% Ce2(CO3)3·6H2O was used as the photoprotector, 36%±2% of MB dye photodegradation was observed after 4 hours of UV irradiation in the photoreactor. This photodegradation amount was reduced to 25%±2% when 1.5 wt% Ce2(CO3)3·6H2O was added as the photoprotector in FIG. 18B. Thus, in FIG. 18B and Table 3, it was confirmed that as the amount of photoprotector Ce2(CO3)3·6H2O was increased, there was correspondingly less photodegradation of MB dye after 4 hours of UV irradiation in the photoreactor. The amount of photodegradation observed has an approximately linear dependence (described by a general equation of the form y(independent variable)=mx(independent variable)+b, where m and b are constants) on the independently variable mass percentage of Ce2(CO3)3·6H2O photoprotector added. This linear correlation is in stark contrast to that observed for the photoprotectant ZnO (NANOBYK-3840) in Figures 19A-19B and Table 3. It was observed that there was little difference in the photodegradation of the MB dye after 4 hours of UV irradiation in the photoreactor when the amount of photoprotectant ZnO (NANOBYK-3840) was increased from 0 (no photoprotectant added) to 1.5 wt%. The latter conclusion is supported by the slight change in the mass percentage of ZnO in the overall ZnO-based sunscreen formulation. The degree of photoprotection provided by Ce2(CO3)3·6H2O was roughly proportional to the amount added, whereas added ZnO (NANOBYK-3840) did not provide photoprotection. While the latter is a UV filter, the former Ce2(CO3)3·6H2O directly scavenges ROS by catalytically decomposing them. These trends in the degree of photoprotection depending on the amount of photoprotectant added for Ce2(CO3)3·6H2O and ZnO (NANOBYK-3840) are summarized graphically in Figure 20. In conclusion, Ce2(CO3)3·6H2O is generally a significantly more potent photoprotectant for MB dyes than ZnO (NANOBYK-3840) when added to ZnO based sunscreen formulations.

[0205] Example 7.3: Preparation of sunscreen films using Congo Red dye and ZnO-based sunscreens with and without UV protection agents and quantification of dye photodegradation In Example 7.2, we observed photoprotection of MB dye, a positively charged dye, using Ce2(CO3)3·6H2O to see whether a similar degree of photoprotection could be obtained with an oppositely charged organic dye (negatively charged). The reason for this is that if the degree of photoprotection does not depend on the charge of the organic dye, one would generally expect photoprotection to be observed regardless of the charge of the organic molecule susceptible to photodegradation. Such results are consistent with the mechanism of action of Ce2(CO3)3·6H2O being the scavenging of photogenerated ROS, rather than an interaction with a photodegradable organic molecule.

[0206] Therefore, using the same setup and ZnO-based sunscreen formulation (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) as in Examples 7.1 and 7.2 above, but using Congo Red (CR) instead of MB dye, the extent of photodegradation due to UV irradiation in a photoreactor was investigated. -3 10 M MB dye (0.6 mL) instead -3A homogeneous composite mixture was prepared by mixing ZnO-based (Neutrogena Sheer Zinc Face™ Mineral Sunscreen SPF 50) sunscreen and CR dye in a manner similar to that described in Example 7.1 for MB, except that M CR dye (0.6 mL) was used. Similarly, a composite sunscreen mixture containing UV protectant was prepared using synthesized Ce2(CO3)3·6H2O (1.5% by weight based on sunscreen weight) according to the procedure in Example 7.2. Photodegradation of CR dye in sunscreen films was also carried out as described in Example 7.1 without UV protectant and as described in Example 7.2 with Ce2(CO3)3·6H2O UV protectant, with the following modifications: First, the CR sunscreen films were dyed salmon on the same filter paper, and the UV exposure time in the photoreactor was 5 hours instead of 4 hours. Second, 2 mL of N,N-dimethylformamide was used for CR dye extraction instead of 2 mL of ethanol used for MB dye extraction. Third, the wavelength used for spectrophotometric measurement of the extracted CR dye was 530 nm.

[0207] The results are shown in Figures 21A-21B and Table 3. In films containing ZnO-based sunscreen on filter paper, the extent of CR dye photodegradation after 5 hours of UV irradiation in a photoreactor was 27 ± 2% without the addition of UV protectant. In films containing 1.5 wt% added Ce2(CO3)3·6H2O, the photodegradation of CR dye was reduced to 9 ± 1% under the same conditions. Thus, Ce2(CO3)3·6H2O photoprotects the CR dye in ZnO-based sunscreen films, just as it photoprotected the oppositely charged MB dye in Example 7.2.

[0208] This result demonstrates the generality of photoprotecting organic molecules regardless of their charge, and therefore, it becomes clear to those skilled in the art that any organic molecule that is sensitive to ROS can be photoprotected by Ce2(CO3)3·6H2O in ZnO-based sunscreen formulations, regardless of its charge.

[0209] Example 7.4: Preparation of sunscreen films using Congo Red dye and titanium dioxide-based sunscreen with and without UV protection agents and quantification of dye photodegradation To further demonstrate the generality of sunscreens that can be used in conjunction with cerium carbonate as a UV protectant, a commercially available TiO2-based sunscreen, Neutrogena® Broad Spectrum Mineral Sunscreen SPF 60+, containing TiO2 (4.9 wt%) and ZnO (4.7 wt%) as active ingredients, was used. Photoreactor experiments were performed exactly as described in Example 7.3 with CR dye, except that films were prepared on filter paper and exposed to UV light in the photoreactor for 4 hours. The films contained no UV protectant, 3.0 wt% Ce2(CO3)3·6H2O synthesized according to Example 3, 3.0 wt% commercially available Ce2(CO3)3·xH2O (Acros Organics), or 3.0 wt% ZnO (NANOBYK-3840). The data are presented in Figures 22A-22D and Table 4 and show that the photodegradation of CR dye is greater with the TiO2-based sunscreen at 40 ± 3% after 4 hours of UV irradiation than with the ZnO-based sunscreen of Example 7.3, which was measured to be 27 ± 2% after 5 hours of UV irradiation. Both were examined in the absence of UV protection. This result is generally consistent with the greater photocatalytic activity of TiO2 relative to ZnO. It was observed that the amount of CR dye photodegradation decreased to 15 ± 1% when Ce2(CO3)3·6H2O, synthesized according to Example 3, was added to a 3 wt% sunscreen formulation. This demonstrates that the effectiveness of cerium carbonate as a UV protection agent in TiO2-based sunscreens is similar to that previously observed in Examples 7.2 and 7.3 for the ZnO-based sunscreens. However, the source of cerium carbonate also significantly affects the degree of photoprotection achieved. A photoprotection of CR dye photodegradation of 24 ± 2% was observed when cerium carbonate consisting of Ce2(CO3)3·xH2O from Acros Organics was used instead of Ce2(CO3)3·6H2O synthesized according to Example 3. The properties of Ce2(CO3)3·xH2O from Acros Organics were assigned in Example 4, again confirming these points in the context of sunscreen-based formulations.Using ZnO (NANOBYK-3840) instead of cerium carbonate as a UV protectant was found to be less effective against the photodegradation of CR dyes, similar to the observations made with MB dye and ZnO-based sunscreens in Example 7.2.

[0210] The amount of Ce2(CO3)3·6H2O synthesized according to Example 3 incorporated into the TiO2-based sunscreen was increased to 5.0 wt %, with the results shown in Figures 23A-23B and summarized in Table 4. Consistent with the results of Example 7.2, increasing the amount of Ce2(CO3)3·6H2O resulted in a nearly proportional increase in the amount of photoprotection provided. There is a slight diminishing return to adding Ce2(CO3)3·6H2O, both here and in Example 7.2, but the effect of increasing Ce2(CO3)3·6H2O on the photoprotection of organic molecules is much more pronounced than with ZnO. Thus, the results of dosing TiO2-based sunscreens with Ce2(CO3)3·6H2O and ZnO are graphed in Figure 24.

[0211] In summary, these data demonstrate the photoprotective action of cerium carbonate in sunscreens based on TiO2 as a UV filter. Here, a similar effect is observed as in ZnO-based sunscreens, and it can therefore be concluded that the nature of the UV filter does not significantly control the action of cerium carbonate as a catalytic scavenger of ROS. Therefore, ZnO-based sunscreens and / or TiO2-based sunscreens containing cerium carbonate as a UV protectant are useful. Furthermore, ZnO-based sunscreens and / or TiO2-based sunscreens containing Ce2(CO3)3·6H2O as a UV protectant are particularly useful.

[0212] [Table 4]

[0213] Example 7.5: Preparation of methylene blue dye and octacrylene-based sunscreen films with and without UV protection agents and quantification of dye photodegradation To further demonstrate the generality of sunscreens that can be used in conjunction with cerium carbonate as a UV protectant, a commercial octacrylene-based sunscreen, Blue Lizard® Kids Australian Sunscreen SPF 30+, with active ingredients consisting of organic UV filters octacrylene (4 wt%) and ZnO (9.7 wt%), was used. Photoreactor experiments were performed exactly as described in Example 7.2 with MB dye, except that films were prepared on filter paper and UV exposure in the photoreactor was performed for 4 hours. The films contained either no UV protectant or 1.5 wt% Ce2(CO3)3·6H2O, synthesized according to Example 3. The slurry formulation for film production, UV light exposure, and MB dye extraction in ethanol were performed as in Example 7.2, except that Blue Lizard® Kids Australian Sunscreen SPF 30+ was used.

[0214] Figure 25A shows the corresponding UV-Visible spectra of the sunscreen film without added UV protection agent at initial time and after 4 hours of UV irradiation in a photoreactor. A 30 nm blue shift in the wavelength of absorbance maximum was observed (from 654 nm initially to 624 nm after 4 hours of UV irradiation in a photoreactor). The degree of photodegradation was calculated by UV-Visible spectroscopy assuming the same extinction coefficient at 654 nm before UV irradiation and at 624 nm after 4 hours of UV irradiation in a photoreactor. The data in Figure 25A corresponds to 64% MB dye photodegradation.

[0215] FIG. 25B shows the corresponding UV-visible spectra of a sunscreen film containing 1.5 wt% Ce2(CO3)3·6H2O synthesized according to Example 3, initially and after 4 hours of UV irradiation in a photoreactor. A 30 nm blue shift was observed in this sample after UV irradiation, similar to the sample without added UV protectant. Since a similar blue shift was observed in the control without photoprotectant, it is inferred that cerium carbonate is not responsible for this shift in the band maximum after UV irradiation in a photoreactor. However, the extent of MB dye photodegradation calculated from the data in FIG. 25B corresponds to 45% MB dye decomposition (using the same assumptions as in the calculation of the degree of MB dye photodegradation from FIG. 25A). This indicates that the addition of 1.5 wt% Ce2(CO3)3·6H2O as a photoprotectant significantly improves the photoprotective efficiency of the sunscreen.

[0216] In summary, Example 7 demonstrates the generality of the photoprotection achieved with Ce2(CO3)3·6H2O as a photoprotectant. This photoprotection extends to sunscreen formulations consisting of different organic molecules and different (ZnO, TiO2, and organic molecule-based) UV filters in a manner that is independent of the charge of the organic molecule. It was observed that Ce2(CO3)3·6H2O synthesized according to Example 3 is preferred in sunscreen applications over the commercial cerium carbonate source described in Example 4, closely resembling the trend of the latter being inferior to the former in Example 4. From the data presented in the above examples, one skilled in the art would conclude that organic molecules susceptible to photodegradation in contact with sunscreen formulations containing cerium carbonate are photoprotected by the consumption of reactive oxygen species that degrade organic molecules, such as on the skin where the sunscreen may be applied topically as a lotion. One skilled in the art would also make this conclusion regardless of whether the sunscreen contains a UV filter, such as ZnO, TiO2, or an organic molecule UV filter, such as octacrylene. A person skilled in the art would also make this conclusion regardless of whether the sunscreen contains organic or inorganic UV filtering agents.Such a person would also make this conclusion regardless of whether the sunscreen contains UV filtering agents.

[0217] Example 7.6: Mammalian cell toxicity to cerium carbonate Ce2(CO3)3·6H2O (micron size) The RBL-2H3 rat cell line was from the Berkeley cell-culture facility. The cells were grown in 35 mm Petri dishes to a confluency of 75. Prior to microscopy, the cells were stored in an air atmosphere at 37°C with 5% CO2. A 10 microliter aliquot of an aqueous dispersion containing 1 mg of cerium carbonate Ce2(CO3)3·6H2O (micron size) in 1 mL of deionized water was added to the RBL-2H3 cells in the Petri dish. Microscopic images of the cells were taken before and 20 minutes after the addition of cerium carbonate. The data shown in Figures 26A-26B show a similar elongated shape of the cells, which is indicative of healthy cells. The viability of the cells appears to be similar both before and after treatment with cerium carbonate Ce2(CO3)3·6H2O (micron size). This means that under the conditions of this experiment, the preferred cerium carbonate, Ce2(CO3)3·6H2O (micron-sized), is generally non-toxic to cells, confirming the general lack of toxicity associated with cerium carbonate.

[0218] Embodiments of the present disclosure In some embodiments, the following is disclosed: 1. Cerium(III) carbonate of formula Ce2(CO3)3·xH2O, where x is zero or a positive number, which during thermogravimetric analysis releases at least 27.6 wt.% CO2 when normalized to the dry mass of the cerium(III) carbonate. 2. The cerium(III) carbonate of embodiment 1, wherein the cerium(III) carbonate is (a) substantially free of cerium(IV); (b) substantially free of cerium oxide phases; or (c) substantially free of cerium(IV) and substantially free of cerium oxide phases. 3. Cerium(III) carbonate according to embodiment 1 or 2, which is white in appearance. 4. Cerium (III) carbonate according to any one of the preceding claims, wherein x is 0, 1, 2, 3, 4, 5 or 6. 5. Cerium(III) carbonate as defined in embodiment 4, wherein x is 4.

[0219] 6. The cerium(III) carbonate according to any one of the preceding claims, wherein the cerium(III) carbonate releases at least 28 wt.% CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium(III) carbonate. 7. The cerium(III) carbonate of embodiment 6, wherein the cerium(III) carbonate releases at least 28.5 wt. % CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium(III) carbonate. 8. The cerium(III) carbonate of any one of the preceding embodiments, wherein the cerium(III) carbonate releases at least 29 wt. % CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium(III) carbonate. 9. A formulation comprising cerium(III) carbonate according to any one of embodiments 1 to 8 and an organic compound that is easily photodegradable.

[0220] 10. A method for inhibiting photolysis of an organic compound, comprising: mixing cerium(III) carbonate according to any one of embodiments 1 to 9 with the organic compound to inhibit photolysis of the organic compound. 11. A preparation containing cerium(III) carbonate and an organic compound that is susceptible to photolysis. 12. The formulation of embodiment 11, wherein the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that releases at least 21.9 wt.% CO2 during thermogravimetric analysis, when normalized to the dry mass of the cerium(III) carbonate source material. 13. The formulation of embodiment 12, wherein the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that releases at least 27.5 wt.% CO2 during thermogravimetric analysis, when normalized to the dry mass of the cerium(III) carbonate source material. 14. The formulation of embodiment 13, wherein the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that releases at least 28.5 wt.% CO2 during thermogravimetric analysis, when normalized to the dry mass of the cerium(III) carbonate source material.

[0221] 15. The formulation of embodiment 14, wherein the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that releases at least 29.0 wt.% CO2 during thermogravimetric analysis, when normalized to the dry mass of the cerium(III) carbonate source material. 16. The formulation of any one of embodiments 11-15, wherein the cerium(II) carbonate is (a) substantially free of cerium(IV); (b) substantially free of cerium oxide phases; or (c) substantially free of cerium(IV) and substantially free of cerium oxide phases. 17. The formulation of any one of embodiments 11-16, wherein the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that is white in color. 18. The formulation of any one of embodiments 11-17, wherein the cerium(III) carbonate is obtained from a cerium(III) carbonate source material that is substantially insoluble in water. 19. The formulation according to any one of embodiments 11 to 18, further comprising a photocatalytically active pigment.

[0222] 20. A formulation according to embodiment 19, wherein the photocatalytically active pigment comprises titanium dioxide. 21. The formulation according to embodiment 19 or 20, comprising from about 1 wt.% to about 20 wt.% of cerium(III) carbonate relative to the amount of photocatalytically active pigment. 22. The formulation of embodiment 21, comprising about 1 wt.% to about 10 wt.% cerium(III) carbonate relative to the amount of photocatalytically active pigment. 23. The formulation of embodiment 22, comprising about 1 wt.% to about 5 wt.% of cerium(III) carbonate relative to the amount of photocatalytically active pigment. 24. The formulation of embodiment 23, comprising about 2 wt.% cerium(III) carbonate relative to the amount of photocatalytically active pigment.

[0223] 25. A formulation according to any one of embodiments 19 to 24, wherein the cerium(III) carbonate is in the same phase as the photocatalytically active pigment. 26. A formulation according to any one of embodiments 19 to 24, wherein the cerium(III) carbonate is in a separate phase from the photocatalytically active pigment. 27. A formulation according to any one of the preceding embodiments, wherein the molar ratio of cerium(III) to cerium(IV) in the formulation is greater than 1.0. 28. A method for producing cerium(III) carbonate, which releases at least 28 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of the cerium(III) carbonate source material, comprising: (i) mixing ammonium carbonate with ammonium cerium(III) nitrate tetrahydrate, ammonium cerium(III) nitrate, or a combination thereof; (ii) washing with water; and (iii) recovering the cerium(III) carbonate from the suspension by centrifugation. 29. The method of embodiment 28, wherein step (i) comprises combining ammonium carbonate and cerium(III) ammonium nitrate tetrahydrate.

[0224] 30. The method of embodiment 28, wherein step (i) comprises mixing ammonium carbonate and ammonium cerium(III) nitrate. 31. The method of any one of embodiments 27-30, comprising combining ammonium carbonate with ammonium cerium(III) nitrate tetrahydrate and / or ammonium cerium(III) nitrate at a pH of about 9.0-9.2 or less. 32. A method for producing cerium (III) carbonate, which releases at least 28 wt. % CO2 during thermogravimetric analysis, when normalized to the dry weight of a cerium (III) carbonate source material, the method comprising: (i) mixing ammonium carbonate and water to form a first solution; (ii) mixing cerium (III) nitrate and water to form a second solution; (iii) mixing the first solution and the second solution to form a third solution, wherein the mixing time for mixing the first solution and the second solution is about 1 minute or less; and (iv) centrifuging the third solution to form cerium (III) carbonate. 33. The method of embodiment 32, wherein the mixing time in step (iii) is about 20 seconds or less. 34. The method of embodiment 32, wherein the mixing time in step (iii) is about 15 seconds or less.

[0225] 35. The method of any one of embodiments 28-34, wherein the cerium(III) carbonate releases at least 28.5 wt. % CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium(III) carbonate. 36. The method of embodiment 35, wherein the cerium(III) carbonate releases at least 29.0 wt. % CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium(III) carbonate. 37. The method of any one of embodiments 28 to 36, wherein the cerium(III) carbonate is Ce2(CO3)3·4H2O. 38. Cerium(III) carbonate produced by the method according to any one of embodiments 28 to 37. 39. A method for producing the formulation of embodiment 11, comprising mixing a cerium(III) carbonate source material and an organic compound susceptible to photodecomposition to produce the formulation.

[0226] 40. The method of embodiment 39, wherein the cerium(III) carbonate source material releases at least 21.9 wt. % CO2 during thermogravimetric analysis, normalized to the dry mass of the cerium(III) carbonate source material. 41. The method of embodiment 40, wherein the cerium(III) carbonate source material releases at least 27.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry mass of the cerium(III) carbonate source material. 42. The method of embodiment 41, wherein the cerium(III) carbonate source material releases at least 28.5 wt. % CO2 during thermogravimetric analysis, when normalized to the dry mass of the cerium(III) carbonate source material. 43. The method of embodiment 42, wherein the cerium(III) carbonate source material releases at least 29.0 wt. % CO2 during thermogravimetric analysis, when normalized to the dry mass of the cerium(III) carbonate source material. 44. The method of any one of embodiments 39 to 43, wherein the cerium(III) carbonate is Ce2(CO3)3·4H2O.

[0227] 45. The method of any one of embodiments 39-44, wherein the cerium(III) carbonate source material is white. 46. ​​The method of any one of embodiments 39-45, wherein the cerium(III) carbonate source material is substantially insoluble in water. 47. The method of any one of embodiments 39-46, wherein the cerium(II) carbonate is (a) substantially free of cerium(IV); (b) substantially free of cerium oxide phases; or (c) substantially free of cerium(IV) and substantially free of cerium oxide phases. 48. The method of any one of embodiments 39 to 47, further comprising mixing the photocatalytically active pigment with the cerium(III) carbonate source material and the decomposable organic compound. 49. The method of embodiment 48, wherein the photocatalytically active pigment comprises titanium dioxide.

[0228] 50. The method of embodiment 48 or 49, wherein the cerium(III) carbonate source material is added in an amount of about 1 wt % to about 20 wt % relative to the amount of photocatalytically active pigment. 51. The method of embodiment 50, wherein the cerium(III) carbonate source material is added in an amount of about 1 wt % to about 10 wt % relative to the amount of photocatalytically active pigment. 52. The method of embodiment 51, wherein the cerium(III) carbonate source material is added in an amount of about 1 wt % to about 5 wt % relative to the amount of photocatalytically active pigment. 53. The method of embodiment 52, wherein the cerium(III) carbonate source material is added in an amount of about 2 wt % relative to the amount of photocatalytically active pigment. 54. The method according to any one of embodiments 48 to 53, wherein the formulation contains cerium(III) carbonate in the same phase as the photocatalytically active pigment.

[0229] 55. The method according to any one of embodiments 48 to 53, wherein the formulation contains cerium(III) carbonate in a separate phase from the photocatalytically active pigment. 56. The method of any one of embodiments 39-55, wherein the molar ratio of cerium(III) to cerium(IV) in the formulation is greater than 1.0.

[0230] In some embodiments, the following is disclosed: 1. A composition comprising cerium(III) carbonate and a pigment or dye or a combination thereof. 2. The composition of embodiment 1, comprising a pigment selected from the group consisting of titanium dioxide, zinc oxide, cerium oxide, zirconium oxide, tungsten oxide, vanadium oxide, tin oxide, nickel oxide, copper oxide, molybdenum oxide, tungsten sulfide, cadmium sulfide, cadmium selenide, zinc sulfide, calcium carbonate, mica, silica, talc, graphite, white lead, barium sulfate, calcium carbonate, lithopone, silica, talc, mica, clay, calcined clay, lead silicochromate, zinc chromate, calcium zinc molybdate, barium metaborate, zinc oxide, zinc sulfide, or combinations thereof. 3. The composition of embodiment 1, wherein the composition comprises a pigment that is titanium dioxide. 4. The composition of embodiment 1, comprising a dye selected from the group consisting of iron oxides, carbon black, cadmium sulfide, toluidene red, chrome orange, chrome yellow, chrome green, polyazaindacenes, coumarins, lanthanide complexes, hydrocarbon and substituted hydrocarbon dyes, polycyclic aromatic hydrocarbons, scintillation dyes, aryl and heteroaryl substituted polyolefins, carbocyanine dyes, phthalocyanine dyes and pigments, oxazine dyes, carbostyril dyes, porphyrin dyes, acridine dyes, anthraquinone dyes, anthrapyridone dyes, naphthalimide dyes, benzimidazole derivatives, arylmethane dyes, azo dyes, diazonium dyes, nitro dyes, quinoneimine dyes, tetrazolium dyes, thiazole dyes, perylene dyes, perinone dyes, bisbenzoxazolylthiophenes, xanthene dyes, indigoid dyes, chromone dyes, flavone dyes, thiazine dyes, and combinations thereof.

[0231] 5. The composition of embodiment 1, comprising a dye selected from the group consisting of iron oxide, carbon black, cadmium sulfide, toluidene red, chrome orange, chrome yellow, chrome green, and combinations thereof. 6. The composition of embodiment 1, comprising a dye that is methylene blue or Congo red. 7. The composition of embodiment 1, wherein the cerium(III) carbonate does not comprise an electrostatically attached carbonate. 8. The composition of embodiment 1, wherein the cerium(III) carbonate releases at least 27.5 wt. % CO2 during thermogravimetric analysis, normalized to the dry weight of the cerium(III) carbonate. 9. The composition of embodiment 1, wherein the cerium(III) carbonate is Ce2(CO3)3·4H2O or Ce2(CO3)3·6H2O.

[0232] 10. A method for producing cerium(III) carbonate comprising mixing a) ammonium carbonate and b) ammonium cerium(III) nitrate in the presence of water. 11. The method of embodiment 10, wherein ammonium carbonate and ammonium cerium(III) nitrate are mixed in the presence of water at a pH of about 9.0 to 9.2. 12. The method of embodiment 10, further comprising mixing the produced cerium(III) carbonate with a dye or pigment, or a combination thereof. 13. The method of embodiment 12, comprising the pigment being titanium dioxide. 14. The method of embodiment 12, comprising a dye selected from the group consisting of iron oxide, carbon black, cadmium sulfide, toluidene red, chrome orange, chrome yellow, chrome green, and combinations thereof.

[0233] 15. The method of embodiment 12, comprising a dye which is methylene blue or Congo red. 16. The method of embodiment 10, wherein the cerium(III) carbonate produced is free of electrostatically attached carbonate. 17. The method of embodiment 10, wherein the cerium(III) carbonate produced releases at least 27.5 wt. % CO2 during thermogravimetric analysis when normalized to the dry mass of the cerium(III) carbonate.

[0234] The section headings used in this disclosure are for organizational purposes only and are not to be construed as limiting the subject matter described. All documents, or portions of documents, cited in this application, including but not limited to patents, patent applications, articles, books, manuals, and papers, are expressly incorporated herein by reference in their entirety for any purpose.

[0235] While various embodiments and aspects have been shown and described in this disclosure, it will be apparent to those skilled in the art that such embodiments and aspects are provided by way of example only. Numerous variations, changes, and substitutions will occur to those skilled in the art. It should be understood that various alternatives to the embodiments described in this disclosure may be employed. Some of the embodiments of the invention related to the present invention are given below. [Embodiment 1] A composition comprising cerium(III) carbonate and a UV protectant. [Embodiment 2] The composition of claim 1 , wherein the UV protection agent comprises a metal oxide. [Embodiment 3] 2. The composition of embodiment 1, wherein the UV protection agent is zinc oxide and / or titanium oxide. [Embodiment 4] 2. The composition of embodiment 1, wherein the UV protection agent is zinc oxide. [Embodiment 5] 2. The composition of embodiment 1, wherein the UV protection agent is titanium dioxide. [Embodiment 6] 6. The composition of any one of the preceding embodiments, wherein the cerium(III) carbonate is present in a concentration of about 0.05% to about 20% by weight. [Embodiment 7] 6. The composition of any one of the preceding embodiments, wherein the cerium(III) carbonate is present in a concentration of about 0.1% to about 15% by weight. [Embodiment 8] 6. The composition of any one of the preceding embodiments, wherein the cerium(III) carbonate is present in a concentration of about 0.5% to about 7% by weight. [Embodiment 9] 9. The composition of any one of the preceding embodiments, wherein the UV protection agent is present in a concentration between 1% w / w and 40% w / w. [Embodiment 10] The cerium(III) carbonate is Ce 2 (CO 3 ) 3 xH 2 0, where x is zero or a positive number. [Embodiment 11] The cerium(III) carbonate is Ce 2 (CO 3 ) 3 ·6H 2 The composition of any one of embodiments 1 to 9, wherein [Embodiment 12] The composition of any one of embodiments 1-11, further comprising avobenzone, methyl anthranilate, ecamsule, octyl methoxycinnamate, homosalate, oxybenzone, sulisobenzone, PABA, padimate O, cinoxate, octyl salicylate, trolamine salicylate, octylocrylene, ensulizole, octyl triazone, enzacamene, amiloxate, dioxybenzone, megizolyl XL, tinosorb S, tinosorb M, NeoHeliopan AP, Uvinal Aplus, or UVAsorb HEB. [Embodiment 13] The composition of any one of embodiments 1 to 12, wherein the composition is a topical lotion. [Embodiment 14] 1. A method for consuming reactive oxygen species synthesized by exposing skin to ultraviolet light, the method comprising placing cerium(III) carbonate on the skin. [Embodiment 15] A method for preventing oxidative damage due to ultraviolet light exposure, comprising topically administering an effective amount of cerium(III) carbonate. [Embodiment 16] The cerium(III) carbonate is Ce 2 (CO 3 ) 3 xH 2 16. The method of embodiment 15, wherein x is O, where x is zero or a positive number. [Embodiment 17] 1. A method for preventing sun damage in a subject due to exposure to ultraviolet radiation, comprising topically administering an effective amount of cerium(III) carbonate. [Embodiment 18] The cerium(III) carbonate is Ce 2 (CO 3 ) 3 xH 2 18. The method of embodiment 17, wherein x is O, where x is zero or a positive number.

Claims

1. A composition comprising cerium(III) carbonate and a UV protectant.

2. The composition of claim 1 , wherein the UV protectant comprises a metal oxide.

3. The composition of claim 1 , wherein the UV protection agent is zinc oxide and / or titanium oxide.

4. The composition of claim 1 , wherein the UV protectant is zinc oxide.

5. The composition of claim 1 , wherein the UV protectant is titanium dioxide.

6. 6. The composition of claim 1, wherein the cerium (III) carbonate is present in a concentration of from 0.05% to 20% by weight.

7. 6. The composition of claim 1, wherein the cerium (III) carbonate is present in a concentration of from 0.1% to 15% by weight.

8. 6. The composition of claim 1, wherein the cerium (III) carbonate is present in a concentration of from 0.5% to 7% by weight.

9. The composition according to any one of claims 1 to 8, wherein the UV protection agent is present in a concentration of from 1% w / w to 40% w / w.

10. The cerium (III) carbonate is Ce 2 (CO 3 ) 3 ・xH 2 The composition of any one of claims 1 to 9, wherein x is zero or a positive number.

11. The cerium (III) carbonate is Ce 2 (CO 3 ) 3 ・6H 2 The composition according to any one of claims 1 to 9, wherein 12. The composition of claim 2, wherein the UV protectant comprises avobenzone, methyl anthranilate, ecamsule, octyl methoxycinnamate, homosalate, oxybenzone, sulisobenzone, PABA, padimate O, cinoxate, octyl salicylate, trolamine salicylate, octylocrylene, ensulizole, octyltriazone, enzacamene, amiloxate, or dioxybenzone.

13. The composition according to any one of claims 1 to 12, wherein the composition is a topical lotion.

Citation Information

Patent Citations

  • Cosmetic

    JP1994145026A

  • Metal oxide solid solution cerium oxide, its production and resin composition and cosmetic comprising the same formulated therein

    JP2000327328A

  • Method for producing platy ceria particle

    JP2010195599A

  • A sunscreen composition containing hydrolyzed jojoba esters to improve water resistance.

    JP2013543478A

  • Sheet-shaped cerium oxide and petal-shaped cerium oxide powder which is aggregate of the sheet-shaped cerium oxide, process for production of the sheet-shaped cerium oxide and the petal-shaped cerium oxide powder, coated sheet-shaped cerium oxide and

    WO2012020729A1